Trem2 regulates macrophage phenotype via the JAK2/STAT3 signaling pathway to ameliorate ventricular remodeling after acute myocardial infarction - Zefeng He; Jing Feng; Ru Yan; Peng Wu; Baozhen Zhu; Huifang Li; Taoyu Yang; Yaxin Lu; Baotong He; Xueping Ma; Shaobin Jia; Guangzhi Cong (Molecular Biology Reports, 2026)

Enhancing weed control in imidazolinone-resistant corn and soybean strip intercropping systems through tank mixtures of imidazolinone and residual herbicides - Yi Ru; Xiangxin Zhuang; Lingyang Feng; Hongyou Wan; Jialin Yu (Crop Protection, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Differential roles of three subclass III C6 transcription factors in the insect-pathogenic lifecycle of Beauveria bassiana - Jian-Ru Feng; Min Li; Sheng-Hua Ying; Ming-Guang Feng (Journal of Invertebrate Pathology, 2026)

Polymer-specific oxidative biotransformation of polyethylene and polypropylene microplastics by the stored-grain pest Tribolium castaneum - Sakhawat Shah; Jin-Ru Zhao; Ze-Yu Liu; Yi-Jia Chen; Jie Tang; Karam Khamis Elgizawy; Qiu-Ying Huang; Elvis Genbo Xu; Feng-Lian Yang (Chemical Engineering Journal, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

The co-ecotoxicity of microplastics and associated contaminants (PFOA) on soil ecosystems - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine; Yi-kai Wang; Jian Su; Jie Chen (Journal of Environmental Chemical Engineering, 2026)

pH-responsive microcapsules co-delivering radioprotectant and probiotics for synergistic mitigation of radiation-induced enteritis - Caifang Gao; Jiaxuan Ma; Luke Ge; Yongle Zhao; Ru Feng; Pengqi Zhu; Jinghua Sun; Ruiping Zhang (Chemical Engineering Journal, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Unveiling an entirety of TFIIH complex comprising Tfb3, Kin28 and Ccl1, and anti-UV and insecticidal activities of Ccl1 in Beauveria bassiana - Min Li; Jian-Ru Feng; Sheng-Hua Ying; Ming-Guang Feng (Pesticide Biochemistry and Physiology, 2026)

A core innate immune gene panel derived from germ-free larval zebrafish transcriptomics resolves strain-specific induction by Aeromonas veronii and Lacticaseibacillus rhamnosus GG - Xiang-Ru Liu; Ying Liu; Chen-Cong Zhang; Zi-Shu Huang; Feng-Yi Guo; De-Sheng Pei (Fish & Shellfish Immunology, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Long non-coding RNAs in exercise: the hidden regulators of adaptation - Qin Zhang; Zhouren Zhang; Cai Ren; Ping Xiang; Xinhua Li; Ru Ren; Lianting Feng; Jicheng Chen (Pflügers Archiv - European Journal of Physiology, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Cadmium disrupts the immune antibacterial function of the freshwater crab Sinopotamon henanense via the Toll/proPO-AS pathway - Yue Liang; Duwen Pei; Cheng Liu; Fenjun Yan; Minnan Bao; Na Liu; Qian Wang; Caiping Feng; Ru Jia; Lan Wang (Journal of Hazardous Materials, 2026)

A novel sterilization mechanism of cold plasma coupled with low-dose ZnO nanoparticles for food Decontamination: Synergistic reactive species generation and zinc ion release - Hang-Bo Xu; Meng-Ru Du; Zhen Jiao; Pan-Feng Guan; Ruo-Nan Ma (Food Microbiology, 2026)

Design optimization of plate anchor for offshore foundation systems - Ru-Ming Feng; Meysam Bayat; Liyun Zhu; Lei Tan (Marine Georesources & Geotechnology, 2026)

Microplastics Inhibit Microbial Abundance and Enzyme Activities in Pb/Cd Co-contaminated Soil: The Alleviating Role of Biochar - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine (Journal of Soil Science and Plant Nutrition, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Curcumol induces autophagy-dependent hepatic stellate cell death through methionine metabolism disruption - Yi-jie Gao; Ya Zhou; Yi-ning Li; Kai-yao Yang; Si-wei Xia; Meng-ru Hu; Yang Li; Li Chen; Fei-xia Wang; Shuai Lu; Na-qi Lian; Shi-zhong Zheng; et al. (Toxicology and Applied Pharmacology, 2026)

Enhanced photocatalytic fuel cell performance via C/WO3/ZnFe2O4 ternary photoanode for simultaneous wastewater degradation and energy harvesting - Yi Xiao; Ru Zhang; Qi Feng; Hailong Gao; Jiawei Ma; Ting Wu; Yongkui Huang; Longjun Xu; Chenglun Liu (Journal of Environmental Management, 2026)

Intensified drought and vegetation-specific responses in the Tianshan Mountains, Central Asia - Huaijun Wang; Yaning Chen; Liang Ren; Zhi Li; Ru Feng; Zhiguo Ren; Yuanqiao Li; Yaxue Yang; Yingping Pan (CATENA, 2026)

Influence of climate change on suitable areas for three Salvia species and their pollinators - Feng-Shi Zhang; Han-Wen Xiao; Ru-Nan Tian (Plant Ecology, 2026)

Synergistic effects of phenylsilane and isopropyl titanate-modified montmorillonite nanofillers on the thermal and flame-retardant properties of PVA films - Jing-Yao Xiao; Lei Huang; Shi-Xiang Xiong; Jian-Feng Lan; Ru-Xin Chen; Long-Long Jin; Ze-Chao You; Bai-yi Chen; Xian-Hui Zhang (Applied Clay Science, 2026)

Multiscale Constitutive Modeling for Rock Brittle–Ductile Transition Under True Triaxial Conditions - Tianzhi Yao; Li Qian; Jianhai Zhang; Ru Zhang; Xianliang Wang; Qijun Hu; Feng Jiang (Rock Mechanics and Rock Engineering, 2026)

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Cross-feeding supports the growth of ammonia-oxidizing bacteria with reduced genomes during evolution - Yiming Feng; Ru Zheng; Lingrui Kong; Zhang Zhang; Baiyizhuo Chen; Sitong Liu (Water Research, 2026)

Three undescribed terpenoids from the aerial parts of Alstonia scholaris - Bing-ru Liu; Chun-xiang Xu; Dan Liu; Yue Feng; Rong-tao Li; Jin-dong Zhong (Phytochemistry Letters, 2026)

Towards an integrated framework for prioritized management of soil heavy metals: Industrial imprints, dispersion, and geological amplification - Qingxin Deng; Jin-Ru Feng; Hong-Gang Ni; Kefeng Huang; Maohai Jiang (Journal of Environmental Chemical Engineering, 2026)

Superoxide dismutase/peroxidase-like MoS2 quantum dots enhance ammonia synthesis by Klebsiella pasteurii - Meng-Xin Zhao; Si-Ru Chen; Shan-Shan Hu; Ting-Ting Liu; Jia-Le Teng; Ya-Wen Yu; Jia-Long Zhang; Xue-Ru Zhou; Qun-Feng Ye; Su-Fang Qin; Le-Xing You (Journal of Environmental Chemical Engineering, 2026)

New strategy for high-value utilization of silver carp skin/bone mixture: Steam explosion combined with stepwise enzymatic hydrolysis to produce endogenous calcium-bound ACE inhibitory peptides - Zijuan Li; Qingxiang Feng; Yanlei Gao; Tao Yin; Juan You; Shanbai Xiong; Ru Liu (Innovative Food Science & Emerging Technologies, 2026)

Genomics-guided exploration of Nesterenkonia sp. CL21 proteases to produce bioactive peptides with antioxidant and α-amylase inhibitory activities from soy sauce cake hydrolysis - Shieh Feng Chen; Cyn Ru Cheah; Ivan Kai Jie Lim; Hongxuan An; Chun Shiong Chong; Ming Quan Lam; Kah Yaw Ee (Food Bioscience, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Experimental study on interaction of track and clayey seabed for deep-sea mining vehicles - Bo-Wen Chen; Ru-Ming Feng; Chao Hou; Wei-Qiang Feng (Ocean Engineering, 2026)

Synergistic inhibition of advanced glycation end products and enhancement of flavor by the combination of oligomeric proanthocyanidins and glycated yeast proteins - Jing-jing Fu; Bo-wen Ru; Qi-cheng Zhang; Yu-jun Wu; Hai-yang Feng; Lian-ping Zheng; Yue-wen Chen (Food Research International, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Rethinking crustacean shell waste valorization: from environmental burden to microbial platform for sustainable bioproducts - Ru-Li He; Dong-Feng Liu (ENGINEERING Environment, 2026)

Metabolic-Epigenetic-Immune axis in Ischemic Stroke: Lactate-derived Lactylation as a Key Regulator - Xin-Yu Dong; Xin-Ru Pan; Xiao-Shuang Feng; Jia-Xin Xie; Xiao-Yi Xiong (Metabolic Brain Disease, 2026)

Calcium chloride inhibits water-soaking disorder of fresh-cut cantaloupe through regulating sugar, organic acid, and anaerobic respiration metabolisms - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2026)

Cissatriterpenoids D-L, nine undescribed polyhydroxylated oleanane triterpenoids from Cissampelos pareira var. hirsuta - Shuang-Qin Cao; Ru-Yi Pan; Tong-Tong Zhang; Jian-Hong Gong; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Xiao-Ke Zheng; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry, 2026)

Efficient Biosynthesis of Selenium-Enriched Saccharomyces cerevisiae via Siderophore-Assisted selenite uptake and biotransformation - Wen-tao Du; Ya-ru Wei; Xue Zhao; Qiang-qiang Gou; Omer Hassan Ali; Wen-di Wang; Jia-nan Xu; Zai-ping Feng; Xin-guo Zhang (Bioresource Technology, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Comparative roles of four TFIIH subunits (Tfb1, Tfb2, Tfb4 and Tfb5) in anti-UV and insecticidal processes of Beauveria bassiana - Min Li; Jian-Ru Feng; Sheng-Hua Ying; Ming-Guang Feng (Pesticide Biochemistry and Physiology, 2026)

Tracking the dynamic changes in vegetation belts in China: spatiotemporal insights into climate and human influences - Yong Xu; Yun-Gui Lu; Qiang-Yu Dai; Wen-Ting Huang; Shang-Chen Zhou; Ru-Long Ma; Wen-Qiang Peng; Yu-Xi Feng (Regional Environmental Change, 2026)

Soil biogeochemical controls on the distribution of phosphorus fractions in the Qilian Mountains of China’s drylands - Zeng-Ru Wang; Ji-Liang Liu; Feng-Rui Li (Plant and Soil, 2026)

Bridging Aquaculture and Human Medicine: A Comprehensive Review of Zebrafish Models for Chronic Kidney Disease - Feng‐Yi Guo; Hao‐Yu Yang; Lan‐Chen Zhang; Xiang‐Ru Liu; Pan‐Pan Jia; De‐Sheng Pei (Reviews in Aquaculture, 2026)
Chronic kidney disease (CKD) poses a significant global health burden, necessitating robust animal models for mechanistic studies and drug discovery. Zebrafish offers unique advantages as a powerful models in kidney disease, including high‐throughput compatibility, optical transparency, and significant genetic and nephron homology with both humans and farmed teleosts. However, challenges, such as the species' potent regenerative capacity and a lack of standardized diagnostic thresholds, hinder their broad application. This review systematically summarizes four principal induction strategies: environmental stress, nephrotoxic chemical exposure, CRISPR/Cas‐based gene editing, and transgenesis. We further outline a validation pipeline that integrates functional assays, morphometrics, and histopathology, while advocating for cross‐laboratory harmonization. Additionally, we compare risk factors for CKD and CKD of unknown etiology (CKDu), emphasizing environmental contributors. Collectively, we propose zebrafish as a reproducible platform for aquaculture applications, specifically for nephropathy early‐warning systems and functional feed assessment, and for human therapeutic research. These standardized models hold great promise for high‐throughput drug screening and elucidating disease mechanisms, facilitating the translation of findings to both aquaculture and clinical medicine.

DcCAMTA6-DcCML8 promotes GABA accumulation in fresh-cut carrots via transcriptional activation of polyamine metabolism genes - Jinglin Zhang; Wanli You; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2026)

Regulatory roles of three Zn(II)2Cys6 cluster-coding genes in insect pathogenicity and environmental fitness of Beauveria bassiana - Jian-Ru Feng; Min Li; Sheng-Hua Ying; Ming-Guang Feng (Pesticide Biochemistry and Physiology, 2026)

Construction of acyl-homoserine lactone-producing engineered bacteria for activating low-temperature anammox process - Jiangwei Wang; Jianhang Zhou; Yiming Feng; Jingqi Sun; Ru Zheng; Kuo Zhang; Juejun Pan; Xiaogang Wu; Liguo Zhang; Sitong Liu (Environmental Research, 2026)

Dual-modal antioxidant nanozyme hydrogel for protection against noise-induced hearing loss via attenuation of oxidative stress and NF-κB/MAPK signaling - Liang Xia; Ru Tang; Yi Chen; Ning Ma; Lili Xiao; Xiaoyan Chen; Xiaoyin Mao; Keyi Li; Yanmei Feng; Jingjing Liu; Amin Zhang (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Spatio-seasonal distribution, precursor transformation, and ecological risks of per- and polyfluoroalkyl substances in port sediments: Insights from a subtropical urban harbor - Chih-Feng Chen; Noralyn G. Dimaongon; Yun-Ru Ju; Chiu-Wen Chen; Yee Cheng Lim; Ming-Huang Wang; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Integrated assessment of trace element enrichment and accumulation in estuarine sediments of southwestern Taiwan using Sr/Ba ratios and pollution indices - Chih-Feng Chen; Noralyn G. Dimaongon; Yee Cheng Lim; Ming-Huang Wang; Yun-Ru Ju; Kent Naiah D. Araña; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

Straw interlayer burial improved soil humic fractions via pore-microbe mediated life strategy hierarchy regulating pore structure and bacterial characteristic in saline soils - Hongyuan Zhang; Jiashen Song; Jie Zhou; Fangdi Chang; Ru Yu; Wenhao Feng; Haoruo Li; Jing Wang; Xiaobin Li; Yuyi Li (Journal of Environmental Management, 2026)

Effects of nighttime warming and nitrogen addition on phytoplankton biomass in a submerged macrophytes-dominated freshwater wetland - Yaru Lyu; Jiayin Feng; Wenjing Ma; Chao Wang; Mengyu Yan; Zixuan Yang; Yunpeng Guo; Jinhua Zhang; Hongpeng Wang; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Journal of Environmental Sciences, 2026)

Microbial-electrochemical driven simultaneous biogas upgrading and high-value medium-chain carboxylic acid production - Ya-Ru Wang; Chuan Chen; Shu-Tong Wu; Zi-Han Wang; Lei Zhao; Juan Tong; Kai-Kai Wu; De-Feng Xing; Ai-Jie Wang; Nan-Qi Ren (Bioresource Technology, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

Pathogenic and beneficial microbial communities determine the shelf life of stored 'Fengtangli' plums - Yu-Ru Wang; Tomislav Cernava; Shi-Xian Zeng; Hong Chen; Feng-Quan Liu; Zheng-Qing Fu; Tao Zhou; Yong Wang; Jia Liu (Postharvest Biology and Technology, 2025)

Exploring the potential of radar vegetation indices for soil parameters retrieval: a case study of remote sensing soil salinity mapping - Aihepa Aihaiti; Ilyas Nurmemet; Yu Qin; Bilali Aizezi; Yang Xiang; Meimei Zhang; Yixin Zhang; Ru Feng (CATENA, 2025)

High Quality, Granular, Timely, Trustworthy and Efficient Vertebrate Species Distribution Data Across a 30,000 km 2 Protected Area Complex - Yinqiu Ji; Alex Diana; Xueyou Li; Eleni Matechou; Jim E. Griffin; Shuwei Liu; Mingjie Luo; Chunying Wu; Ru Bai; Chenyang Yao; Tingting Yin; Feng Dong; et al. (Ecology Letters, 2025)
The routine generation of species distribution data at scale remains a challenge. We used aquatic environmental DNA metabarcoding to sample vertebrate species across the 30,000 km 2 Gaoligongshan region along the China–Myanmar border. In just 56 calendar days (33 researcher‐field‐days + 69 researcher‐lab‐days), we detected 389 vertebrate species, of which 35 are Red‐Listed. We introduce the ‘eDNA‐aware’ OccPlus occupancy model, which accounts for false‐negative and false‐positive error in the field and lab. OccPlus leverages the taxonomic breadth of eDNA datasets by using ordination to estimate species occupancies. We recover known biogeographic patterns and find that native terrestrial and fish species have higher occupancies inside protected areas while domesticated species and non‐native fishes have higher occupancies outside them. Our study demonstrates how eDNA metabarcoding can obtain high‐quality, granular, timely, trustworthy and efficient species distribution data to facilitate nature conservation and restoration.

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

CaCl2 alleviates water-soaking disorder by attenuating mitochondrial oxidative damage in fresh-cut cantaloupe - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2025)

Regional coordination for emission reduction and energy supply in transition: A spatiotemporally adaptive policy framework based on markets dynamic reconstruction - Baojun Tang; Huchen Feng; Ru Li (Energy Policy, 2025)

Underwater-adhesive and mechanically reinforced porous amidoxime hydrogel for fast and selective uranium extraction from seawater - Xue Bai; Pan Wang; Ru Feng; Jianming Pan; Yonghui Sun (Desalination, 2025)

Ionic liquids accelerate the crystallization of a magnetic fluorine-functionalized 3D covalent organic framework for efficient capture of trace benzoylurea insecticides in juices and beverages - Zekun Liu; Lu Liu; Yan Dong; Yan Li; Chong Zhang; Xiao-Li Wang; Lingxi Zhao; Hai-Long Jiang; Yong-Ning Wu; Xiangfeng Chen; Feng Li; Ru-Song Zhao (Chemical Engineering Journal, 2025)

Particulate pollution in underground restaurants with increased use of prefabricated dishes: Characteristics and influential factors - Yiyun Zhuang; Almira Anwar; Zhe Li; Ru Zhang; Feng Shi; Yuehua Lin; Chen Chen; Bin Zhao (Building and Environment, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

LsMYB44 and LsWRKY75 regulate phenolic accumulation in fresh-cut stem lettuce treated with γ-aminobutyric acid (GABA) - Xueyin Ru; Jinglin Zhang; Wanli You; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

Effect of exogenous DNP and ATP on storage quality, endogenous energy status and phenolic biosynthesis of shredded cucumber - Wanli You; Yiting Chen; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Journal of Stored Products Research, 2025)

Electrocatalytic synergistic degradation of tetracycline by low-energy-consumption Mn0.22-NiS nanosheet electrodes: Interface mechanism and toxicity analysis - Fan-Hao Hu; Qun-Feng Ye; Si-Ru Chen; Ya-Wen Yu; Hao Chen; Su-Fang Qin; Le-Xing You; Xiao-Chun Tian; Feng Zhao (Chemical Engineering Journal, 2025)

Efficient Microbial Production of Selenium Nanoparticles by Selenium-Tolerant Alcaligenes sp. HZ-9-3-3 - Omer Hassan Ali Hassan; Ya-Ru Wei; Zai-Ping Feng; Jia-Mei Pei; Jia-Nan Xu; Wen-Tao Du; Qiang-qiang Gou; Wen-Di Wang; Xue Zhao; Qin-Cui Shi; Xin-Guo Zhang (Current Microbiology, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

6-Methoxydihydrosanguinarine Suppresses the Proliferation of Non-small Cell Lung Cancer Cells through Elevation of ROS and Activation of IRE1/JNK Signaling - Xiao Qi; Chong Niu; Zi-zheng Zhang; Meng-ru Chen; Feng-ze Wang; Hong-rong Fei (Cell Biochemistry and Biophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Improved antifouling and regeneration capability of polyaniline-modified halloysite nanotube/MXene composite membranes - Jing-Yi Feng; Wen-Hao Geng; Ru-Yu Chang; Yu-Han Wang; Yue-Xin Wang; Ze-Long Bao; Wen-Yi Sun; Lu-Yao Tian; Di Zhang; Hong-Zhang Geng (Journal of Water Process Engineering, 2025)

Efficient removal of dissolved tri-n-butyl phosphate from aqueous solution by immobilized bacterial microspheres - Si-Yi Ren; Zhao-Xing Peng; Jin-Ru Feng; Xi-Ming Zeng; Hong-Gang Ni (Journal of Environmental Management, 2025)

Ilimaquinone induces apoptosis in gastric cancer cells by inhibiting the signal transducer and activator of the transcription 3 pathway - Jui-Hsin Su; Li-Yuan Bai; Chia-Yung Wu; Chia-Hsien Feng; Jing-Ru Weng (Chemico-Biological Interactions, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Different responses of phytoplankton taxa to water N and P inputs in a freshwater wetland: A mesocosm study - Wenjing Ma; Jiayin Feng; Jinhua Zhang; Hongpeng Wang; Yunpeng Guo; Yaru Lyu; Chao Wang; Zixuan Yang; Mengyu Yan; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Marine Pollution Bulletin, 2025)

Unraveling the crucial role of Al distribution in ordered mesoporous silica for ultra-stable CO2 adsorption - Xu Li; Xiangyu Li; Ru Feng; Miaomiao Tan; Yu Feng; Mengmeng Wu; Weiren Bao; Liping Chang; Jiancheng Wang (Chemical Engineering Journal, 2025)

Engineering an Ag2Se@PANi core–shell nanozymes – Klebsiella pasteurii hybrid system with enhanced ammonia synthesis - Meng-Xin Zhao; Si-Ru Chen; Bo Hu; Hao Chen; Ya-Xuan Xiao; Ting-Ting Liu; Shan-Shan Hu; Su-Fang Qin; Xuee Wu; Le-Xing You; Feng Zhao (Bioresource Technology, 2025)

Mitigating low-temperature frost damage in Taiwan high-altitude tea cultivation: physiological insight and protective strategies - Po-Heng Chen; Ru-Hong Lin; Chui-Feng Chiu; Yu-Sheng Lin (Planta, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Construction and application of antimicrobial ultrafiltration membranes based on electro-stimulated hollow mesoporous carbon spheres and carbon nanotubes - Ru-Yu Chang; Wen-Hao Geng; Li-Chao Jing; Jing-Yi Feng; Yue-Xin Wang; Peng-Fei Qian; Ze-Long Bao; Wenyi Wang; Di Zhang; Hong-Zhang Geng (Journal of Environmental Chemical Engineering, 2025)

Granitoid genesis and related rare metal mineralization of the Shihuiyao Rb–Ta–Nb deposit in the Southern Great Xing’an Range, NE China - Shi-Heng Bai; Yu Huang; Zhi-Jie Feng; Matthew J. Brzozowski; Yao-Hui Jiang; Ru-Xiong Lei; Chang-Zhi Wu (Gondwana Research, 2025)

Metal-organic coordinated self-assembled nanomedicine for enhanced cuproptosis-mediated chemo-photo-chemodynamic synergistic therapy of non-small cell lung cancer - Ru-Gui Liu; Rui-Rui Zhao; Zi-Wei Yu; Feng-Juan Liu; Chun-Zhao Liu; Xiao Wu (Chemical Engineering Journal, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Efficient fluconazole degradation by activating peroxymonosulfate with LDH-coated nickel foam: Synergism of radical and non-radical pathways - Xiang-Yang Li; Ling-Xi Zhao; Meng Xie; Ning Liu; Xiang-Feng Chen; Ru-Song Zhao (Journal of Water Process Engineering, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Mechanism of enhanced quality of Acetes chinensis powder-Alaska Pollock surimi: Gel properties, rheological properties, micro-structure - Qianqian Li; Jiehui Feng; Ru Jia; Huamao Wei; Tao Huang; Jinjie Zhang; Dalun Xu; Wenge Yang; Gaoshang Li (Food Research International, 2025)

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Efficient adsorption behavior of Fe-based ternary magnetic LDHs for naphthalene acetic acid: Role of Fe element - Ning Liu; Ti-Bo Fang; Ling-Xi Zhao; Na Li; Xiang-Feng Chen; Ru-Song Zhao (Environmental Research, 2025)

Dissimilatory nitrate reduction to ammonium driven by different electron donors: Mechanisms, recent advances, and future perspectives - Wan-Ru Wen; Tian-Chen Liu; Sheng-Qiang Fan; Xin Tan; Yang Lu; De-Feng Xing; Bing-Feng Liu; Nan-Qi Ren; Guo-Jun Xie (Chemical Engineering Journal, 2025)

Modeling Li isotope fractionation during the coal-combustion process and evaluating its capacity as an environmental tracer - Jing Chen; Yilin Xiao; Jack Geary Murphy; Dong-Bo Tan; Yang-Yang Wang; Biao Fu; Guijian Liu; Ru-Wei Wang; Xiaoxia Wang; Feng-Tai Tong (Chemical Geology, 2025)

Rapid, green and semi-automated PT-μSPE for antidepressants analysis in urine and plasma using melt-blown polypropylene from disposable face masks as sorbent - Qianwei Li; Bowen Deng; Ru Feng; Di Chen; Linlin Hua (Sustainable Chemistry and Pharmacy, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Evaluation on the antibacterial activity of glycyrrhizin against Pseudomonas plecoglossicida in ayu fish (Plecoglossus altivelis) - Fan Tao; Jia-Feng Cao; Yan-Jun Liu; Ru-Yi Chen; Jin-Jin Shi; Chang-Yun Li; Jian-Fei Lu; Guan-Jun Yang; Jiong Chen (Aquaculture, 2025)

Phase transfer and photodegradation of DBP in water–sediment systems explored by compound-specific isotope analysis - Jin-Ru Feng; Hong-Gang Ni (Chemical Engineering Journal, 2025)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Mechanistic insights into the efficient activation of peracetic acid by mackinawite (FeS) for diclofenac degradation under near-neutral conditions: Multiple identification and contribution of non-radicals - Yao-Feng Gao; Yan-Ping Duan; Yu-Ru Chen; Yuan-Hua Jia; Yao-Jen Tu; Chao-Meng Dai (Chemical Engineering Journal, 2024)

Advanced growing-season precipitation peak promotes soil nitrogen mineralization in a semi-arid grassland - Jiayin Feng; Xiaojing Yue; Benqing Li; Jingyi Ru; Zhenxing Zhou; Lingjie Kong; Jiajun Zhang; Jiaxin Zhou; Guilin Zhou; Wenjing Ma; Yaru Lyu; Jian Song; et al. (CATENA, 2024)

Effect of Sodium Alginate and Calcium Chloride on the Physicochemical Characteristics of Shrimp (Penaeus Vannamei) Surimi Gels - Ziyan Wang; Jiehui Feng; Qianqian Li; Ru Jia; Tao Huang; Huamao Wei; Wenge Yang (Journal of Ocean University of China, 2024)

Clarifying the impacts of climatic coupling on plastic-mulching potato production in the loess plateau of China - Zhihao He; Kaiyuan Gong; Mengyu Qu; Xiaoya Ru; Shang Chen; Tengcong Jiang; Jing Zhang; Hao Feng; Qiang Yu; Liang He; Jianqiang He (Agricultural Systems, 2024)

Classification method of infrasound events based on the MVIDA algorithm and MS-SE-ResNet - Xiao-Feng Tan; Xi-Hai Li; Chao Niu; Xiao-Niu Zeng; Hong-Ru Li; Tian-You Liu (Applied Geophysics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Response of anammox to organics with different degradation characteristics and exposure time: Performance, sludge characteristics and bacterial community - Shuai Zhang; Long-Yun Lai; Tian-Xiang Wang; Wei-Lei Jin; Ru-Ru Yi; Dong-Zhi Chen; Ren-cun Jin; Guang-feng Yang (Science of The Total Environment, 2024)

Experimental study on the influence of particle morphology on compression characteristics of coral sand in South China Sea - Ru Qu; Cheng-hao Ma; Chang-qi Zhu; Hai-feng Liu (Ocean Engineering, 2024)

A multi-objective operation optimization method for dynamic control of reservoir water level in evolving flood season environments - Li Zhang; Zhong-kai Feng; Xin-ru Yao; Wen-jing Niu; Yong-qiang Wang; Li Mo (Journal of Hydrology, 2024)

γ-aminobutyric acid treatment inhibits browning and promotes storage quality by regulating reactive oxygen species and membrane lipid metabolism in fresh-cut stem lettuce - Xueyin Ru; Wanli You; Jinglin Zhang; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2024)

Effects of dielectric barrier discharge cold plasma treatment on quality maintenance, energy and γ-aminobutyric acid accumulation of fresh-cut carrots - Wanli You; Xianwei Meng; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Control, 2024)

Dissect the association between per- and polyfluoroalkyl substances (PFAS) and kidney function from the perspective of lipid molecules - Yi-Ran Chen; Shao-Bin Lin; Jia-Yun Lv; Yan Wu; Wen-Ru Feng (Environmental Pollution, 2024)

Nickel sulfide nanorods encapsulated in Nitrogen-Doped carbon on nickel foam in situ derived from Saccharomycetes cerevisiae for the selective oxidation of biomass - Hao Chen; Si-Ru Chen; Qing Yang; Le-Xing You; Qun-Feng Ye; Ai-Jun Wang; Dong-Hai Lin; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2024)

Changes in plant litter and root carbon inputs alter soil respiration in three different forests of a climate transitional region - Jiayin Feng; Chunyu Wang; Jingjing Gao; Huixia Ma; Zheng Li; Yuanfeng Hao; Xueli Qiu; Jingyi Ru; Jian Song; Shiqiang Wan (Agricultural and Forest Meteorology, 2024)

Single and mixture toxicity of benzophenone-3 and its metabolites on Daphnia magna - Yun-Ru Ju; Chang-Rui Su; Chih-Feng Chen; Cheng-Fu Shih; Li-Siang Gu (Chemosphere, 2024)

Fruit flexible collecting trajectory planning based on manual skill imitation for grape harvesting robot - Jiahui Sun; Qingchun Feng; Yifan Zhang; Mengfei Ru; Yajun Li; Tao Li; Chunjiang Zhao (Computers and Electronics in Agriculture, 2024)

A bifunctional thiobenzamide additive for improvement of cathode kinetics and anode stability in lithium-sulfur batteries - Junpeng Rao; Tong Yu; Youshuang Zhou; Ru Xiao; Yaozu Wang; Zhuoyan Qu; Dean Shi; Zhenhua Sun; Feng Li (Chemical Engineering Journal, 2024)

Understanding the evolution of molybdenum-nitrogen doped carbon with long-term durability for efficient oxygen reduction reaction - Xingyu Luo; Bingbao Mei; Ru Feng; Xiaofeng Xu; Zhongyan Zhang; Mingyu Ou; Fanfei Sun; Huajun Zheng; Meiqin Shi (Chemical Engineering Journal, 2024)

High-transmittance, fast-response, colored smart windows based on lateral-driving electrophoretic display - Yue Zhang; Jinglan Yang; Feng Xiong; Debo Zeng; Tao Zhou; Jintao Shi; Bo-Ru Yang (Chemical Engineering Journal, 2024)

Improved prediction of swimming talent through random forest analysis of anthropometric and physiological phenotypes - Cheng Liu; Bingxiang Xu; Kang Wan; Qin Sun; Ruwen Wang; Yue Feng; Hui Shao; Tiemin Liu; Ru Wang (Phenomics, 2024)

Development and application of bisphenol S electrochemical immunosensor and iridium oxide nanoparticle-based lateral flow immunoassay - Zhenzhong Zhang; Yongliang Feng; Hayan Teng; Shaoguo Ru; Yuejiao Li; Minhao Liu; Jun Wang (Chemosphere, 2024)

Do government resource management policies influence green productivity? New perspectives from fintech and digital resource policy in China - Pei Liu; Shiyu Feng; Yueze Liu; Xue Ru; Shengli Zhang (Resources Policy, 2024)

Refining metallic nano-copper by electron-rich black carbon for superior Fenton-like catalysis in water purification: The capacitive regulation of corrosive electron transfer - Lu Zhao; Xing-Bo Chen; Xin-Ru Hu; Lei Chen; Shun Feng; Ai-Yong Zhang; Shu-Chuan Peng; Zhi-Xian Lin; Chu Jiang; Wei Da; Qi-Xin Wei (Journal of Hazardous Materials, 2024)

Pollution level and ecological risk assessment of triazine herbicides in Laizhou Bay and derivation of seawater quality criteria - Zhenzhong Zhang; Yongliang Feng; Weizhong Wang; Shaoguo Ru; Lingchao Zhao; Yuanqing Ma; Xiukai Song; Lijuan Liu; Jun Wang (Journal of Hazardous Materials, 2024)

Additive effects of N addition and changing precipitation on soil respiration in a climate transitional forest - Jiayin Feng; Jingjing Gao; Huixia Ma; Chunyu Wang; Yuanfeng Hao; Zheng Li; Jingru Zou; Xueli Qiu; Jingyi Ru; Jian Song; Shiqiang Wan (CATENA, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Performance evaluation of vegetation concrete with carbonaceous mudstone aggregates in slope protection under wet-dry conditions - Ling Zeng; Jin-Tao Luo; Zi-Ru Yang; Hui-Cong Yu; Wei Wen; Qian-Feng Gao; Hong-Ri Zhang (Bulletin of Engineering Geology and the Environment, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Accurate and precise in situ determination of beryllium contents in beryllium minerals using ablation spot size of 13 μm by LA–ICP–MS - Wen-Kai Jin; Xu-Dong Che; Ru-Cheng Wang; Huan Hu; Can Rao; Wen-Lan Zhang; Xiao-Feng Li (Journal of Geochemical Exploration, 2024)

Spatially confined conjugation of enzyme immobilized magnetic nanochains with poly(vinylphosphonic acid) polymers using droplet reactors for uranium extraction - Danqing Shen; Qian Du; Pan Wang; Xiaohua Tian; Yue Wang; Ru Feng; Jianming Pan (Chemical Engineering Journal, 2024)

Distance-decay equations of antibiotic resistance genes across freshwater reservoirs - Zhao-Feng Guo; Kiranmoy Das; Wiebke J. Boeing; Yao-Yang Xu; Edoardo Borgomeo; Dong Zhang; Si-Cheng Ao; Xiao-Ru Yang (Water Research, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Exogenous CaCl2 delays flesh softening by inhibiting the degradation of cell wall in fresh-cut cantaloupe - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2024)

Chemical constituents with antioxidant activity from the branches and leaves of Hultholia mimosoides - Ru Feng; Jia-Xin Xu; Xiao-Yi Luan; Xiao-Ning Wang; Tao Shen; Dong-Mei Ren; Xiao-Ling Wang (Phytochemistry, 2024)

Response model between nanobubble preparation parameters and properties: Controllable preparation & its application example - Xin Ru Feng; Jiajun Hu; Nan Liu; Wang Kai Tong; Mintian Gao; Chaomeng Dai; Yueming Han; Jixiang Li (Journal of Water Process Engineering, 2024)

Exogenous chlorogenic acid inhibits quality deterioration in fresh-cut potato slices - Wanli You; Chunfei Wang; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Visible-light-driven photocatalytic degradation of ibuprofen by Cu-doped tubular C3N4: Mechanisms, degradation pathway and DFT calculation - Zhi-Bang Lv; Jiao Feng; Ru-Jin Zhao; Jun-Jian Shen; Wen-Wen Yang (Chemosphere, 2024)

Prediction of acute toxicity for Chlorella vulgaris caused by tire wear particle-derived compounds using quantitative structure-activity relationship models - Jie-Ru Jiang; Wen-Xi Cai; Zhi-Feng Chen; Xiao-Liang Liao; Zongwei Cai (Water Research, 2024)

Dual-role KCl-assisted fabrication of porous carbon with controllable architecture from coal liquefaction residue for supercapacitors - Xiaoxia Yang; Guoxiao Sun; Fei Wang; Long Chen; Zhuangzhuang Zhang; Yanzhong Zhen; Danjun Wang; Feng Fu; Ru’an Chi (Fuel, 2024)

Glutamate application maintains quality and antioxidant capacity of fresh-cut carrots by modulating GABA shunt, phenylpropanoid and ROS metabolism - Jinglin Zhang; Jing Zhao; Xiaoxia Zuo; Wanli You; Xueyin Ru; Feng Xu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Candidate gene mining of GA-mediated regulation of pear fruit shape - Zeyu Xue; Ru Yang; Yadong Wang; Yuchen Ma; Yujing Lin; Zhengao Li; Yuqin Song; Xinxin Feng; Liulin Li (Horticulture, Environment, and Biotechnology, 2024)

Application of a water-energy-carbon coupling index to evaluate the long-term operational stability of the anaerobic-anoxic-oxic-membrane bioreactor (A2/O-MBR) process under the influence of rainstorms - Lian Yu; Kaiming Peng; Yizhen Huang; Feng Chen; Shoubin Chen; Yulong Xia; Xiangfeng Huang; Xiaojing Ni; Ru Guo; Chen Cai; Jia Liu (Water Research, 2024)

Blue-light irradiation induced partial nitrification - Ru Zheng; Yiming Feng; Lingrui Kong; Xiaogang Wu; Jianhang Zhou; Liguo Zhang; Sitong Liu (Water Research, 2024)

Nighttime warming and nitrogen addition effects on the microclimate of a freshwater wetland dominated by Phragmites australis - Yunpeng Guo; Jian Song; Jiayin Feng; Hongpeng Wang; Jinhua Zhang; Jingyi Ru; Xiaopan Wang; Xu Han; Huixia Ma; Yaru Lyu; Wenjing Ma; Chao Wang; et al. (Science of The Total Environment, 2024)

Anhydride esterification to regulate water migration and reduce ice crystal formation in κ-carrageenan gel during freezing - Xinwei Xu; Feng Jiang; Kuncheng Lin; Jingjing Fang; Fuquan Chen; Yi Ru; Huifen Weng; Qiong Xiao; Qiuming Yang; Anfeng Xiao (Food Hydrocolloids, 2024)

Uptake, translocation, and metabolism of organophosphate esters (OPEs) in plants and health perspective for human: A review - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yu-Fei Feng; Long-Wei Zhang; Xue-Yi Jiang; Yi-Shan Liu; Dong-Wei Wu; Jun-Jie Hu (Environmental Research, 2024)

Comparative evaluation of acid-resistant nanofiltration membranes for heavy metal removal in acidic wastewater - Chun Cui; Cong Luo; Tian Tian; Ru Feng; An-Kang Li; Shi-Peng Sun; Xue-Li Cao (Desalination, 2024)

Redirecting surface reconstruction of CoP-Cu heterojunction to promote ammonia synthesis at industrial-level current density - Li Gan; Xiaoxue Zhang; Lei Guo; Muhammad Ajmal; Ru Jia; Xiaolei Guo; Chengxiang Shi; Lun Pan; Faryal Idrees; Xiangwen Zhang; Zhen-Feng Huang; Guidong Yang; et al. (Chemical Engineering Journal, 2024)

Vital residues-orientated rational design of butenolide inhibitors targeting Of ChtI - Qing Han; Yun-Jiang Zi; Tian-Yu Feng; Nan Wu; Ren-Xuan Zou; Jing-Yu Zhang; Ru-Lei Zhang; Qing Yang; Hong-Xia Duan (Medicinal Chemistry Research, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Nitrogen addition does not alter symmetric responses of soil respiration to changing precipitation in a semi-arid grassland - Lingjie Kong; Jian Song; Jingyi Ru; Jiayin Feng; Jiawei Hou; Xueke Wang; Qingshan Zhang; Haidao Wang; Xiaojing Yue; Zhenxing Zhou; Dasheng Sun; Jiajia Zhang; et al. (Science of The Total Environment, 2024)

Carbon tax and low-carbon credit: Which policy is more beneficial to the capital-constrained manufacturer's remanufacturing activities? - Zhan-Jie Wang; Ru-Fu Zhou; Yong-Feng Ma; Yong-Jian Wang (Environmental Research, 2024)

Effects of heavy metals and metalloids on the biodegradation of organic contaminants - Jin-Ru Feng; Hong-Gang Ni (Environmental Research, 2024)

Ecological risk assessment of heavy metals in desulfurized seawater discharged from a coal-fired power plant in Qingdao - Yongliang Feng; Yiran Ru; Jun Wang; Xiaona Zhang; Hua Tian; Shuhe Lei; Ziang Zhao; Shaoguo Ru (Ecotoxicology, 2024)

Conductive nanofiltration membranes via in situ PEDOT-polymerization for electro-assisted membrane fouling mitigation - Tian-Zhi Jia; Ru Feng; Chun Cui; Qian Chen; Levente Cseri; Rong-Fei Zhou; Gyorgy Szekely; Xue-Li Cao; Shi-Peng Sun (Water Research, 2024)

Communication mediated interaction between bacteria and microalgae advances photogranulation - Xiaogang Wu; Lingrui Kong; Yiming Feng; Ru Zheng; Jianhang Zhou; Jingqi Sun; Sitong Liu (Science of The Total Environment, 2024)

Calcium chloride treatment maintains quality and enhances antioxidant capacity of fresh-cut carrots through modulating DcCMLs-DcCAMTA3-mediated phenylpropanoid pathway - Jinglin Zhang; Xiaoxia Zuo; Yanfei Li; Xueyin Ru; Wanli You; Feng Xu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Comprehensive evaluation of antibiotics pollution the Yangtze River basin, China: Emission, multimedia fate and risk assessment - Yu-Ru Chen; Yan-Ping Duan; Zhi-Bo Zhang; Yao-Feng Gao; Chao-Meng Dai; Yao-Jen Tu; Jun Gao (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Integrated transcriptome and metabolome analysis revealed that HaMYB1 modulates anthocyanin accumulation to deepen sunflower flower color - Siqi Ma; Hanlin Zhou; Tingting Ren; Er-ru Yu; Bin Feng; Juying Wang; Chengsheng Zhang; Chao Zhou; Yiqiang Li (Plant Cell Reports, 2024)
Key message HanMYB1 was found to play positive roles in the modulation of anthocyanins metabolism based on the integrative analysis of different color cultivars and the related molecular genetic analyses. Abstract As a high value ornamental and edible crop with various colors, sunflowers ( Helianthus annuus L.) provide an ideal system to understand the formation of flower color. Anthocyanins are major pigments in higher plants, which is associated with development of flower colors and ability of oxidation resistance. Here, we performed an integrative analysis of the transcriptome and flavonoid metabolome in five sunflower cultivars with different flower colors. According to differentially expressed genes and differentially accumulated flavonoids, these cultivars could be grouped into yellow and red. The results showed that more anthocyanins were accumulated in the red group flowers, especially the chrysanthemin. Some anthocyanins biosynthesis-related genes like UFGT (UDP-glycose flavonoid glycosyltransferase) also expressed more in the red group flowers. A MYB transcriptional factor, HanMYB1, was found to play vital positive roles in the modulation of anthocyanins metabolism by the integrative analysis. Overexpressed HanMYB1 in tobacco could deepen the flower color, increase the accumulation of anthocyanins and directly active the express of UFGT genes. Our findings indicated that the MYB transcriptional factors provide new insight into the dynamic regulation of the anthocyanin biosynthesis in facilitating sunflower color formation and anthocyanin accumulation.

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

ABA functions in low phosphate-induced anthocyanin accumulation through the transcription factor ABI5 in Arabidopsis - Ru-Feng Song; Xiao-Yu Hu; Wen-Cheng Liu; Hong-Mei Yuan (Plant Cell Reports, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Peduncle collision-free grasping based on deep reinforcement learning for tomato harvesting robot - Yajun Li; Qingchun Feng; Yifan Zhang; Chuanlang Peng; Yuhang Ma; Cheng Liu; Mengfei Ru; Jiahui Sun; Chunjiang Zhao (Computers and Electronics in Agriculture, 2024)

A novel eco-friendly strategy for removing phenanthrene from groundwater: Synergism of nanobubbles and rhamnolipid - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Xueji You; Xin Ru Feng; Zhi Li; Lang Zhou; Yalei Zhang; Xiaoying Lai; Long Kahon; et al. (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Does biogas industrial policy promote the industrial transformation? - Erga Luo; Ru Yan; Yaping He; Zhen Han; Yiyu Feng; Wenrong Qian; Jinkai Li (Resources Policy, 2024)

CaCl2 promoted phenolics accumulation via the CmCAMTA4-mediated transcriptional activation of phenylpropane pathway and energy metabolism in fresh-cut cantaloupe - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Study and application of coupling relationship between water-salt-resistivity-soil structure in saline soils in arid and semi-arid areas of northwest China - Yang Liu; Feng-jie Li; Hong-li Liu; Yu-ru Hou; Nusrat Nazir (Environmental Research, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

Comammox plays a functionally important role in the nitrification of rice paddy soil with different nitrogen fertilization levels - Kai Zhang; Hui-Feng Sun; You-Cai Kang; Ran Jiang; Yan-Ren Wang; Ru-Yi Zhang; Sheng-Nan Zhang; Yang-Yang Li; Peng Li; Fan Yang; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Genome resources for the elite bread wheat cultivar Aikang 58 and mining of elite homeologous haplotypes for accelerating wheat improvement - Jizeng Jia; Guangyao Zhao; Danping Li; Kai Wang; Chuizheng Kong; Pingchuan Deng; Xueqing Yan; Xueyong Zhang; Zefu Lu; Shujuan Xu; Yuannian Jiao; Kang Chong; et al. (Molecular Plant, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Antioxidant CeO2 doped with carbon dots enhance ammonia production by an electroactive Azospirillum humicireducens SgZ-5T - Gao-Kai Wu; Meng-Xin Zhao; Si-Ru Chen; Yi-Nan Sun; Su-Fang Qin; Ai-Jun Wang; Qun-Feng Ye; Hend Alwathnani; Le-Xing You; Christopher Rensing (Chemosphere, 2023)

Microplastics in coral reef sediments underestimated? They may hide in biominerals - Chih-Feng Chen; Yun-Ru Ju; Chiu-Wen Chen; Frank Paolo Jay B. Albarico; Yee Cheng Lim; Chongtai Ke; Yu-Rong Cheng; Cheng-Di Dong (Science of The Total Environment, 2023)

Cyclodextrin-based metal-organic framework materials: Classifications, synthesis strategies and applications in variegated delivery systems - Ru-nan Zhao; Bei-wei Zhu; Yu Xu; Song-feng Yu; Wen-jun Wang; Dong-hong Liu; Jiang-ning Hu (Carbohydrate Polymers, 2023)

YOLACTFusion: An instance segmentation method for RGB-NIR multimodal image fusion based on an attention mechanism - Cheng Liu; Qingchun Feng; Yuhuan Sun; Yajun Li; Mengfei Ru; Lijia Xu (Computers and Electronics in Agriculture, 2023)

Deep insights into the population shift of n-DAMO and Anammox in granular sludge: From sidestream to mainstream - Sheng-Qiang Fan; Wan-Ru Wen; Guo-Jun Xie; Yang Lu; Bing-Feng Liu; De-Feng Xing; Jun Ma; Nan-Qi Ren (Water Research, 2023)

The interaction between DcCaM7 and DcCAMTA6 promotes γ-aminobutyric acid (GABA) accumulation via regulating GABA shunt in fresh-cut carrots - Jinglin Zhang; Yanfei Li; Xiaoxia Zuo; Xueyin Ru; Wanli You; Feng Xu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2023)

The sulfate assimilation and reduction of marine microalgae and the regulation of illumination - Wen-Ying Dai; Lu Han; Pei-Feng Li; Qin-Dao Li; Li-Jun Xie; Chun-Ying Liu; Jun-Ru Kong; Ru Jia; Dan-Yang Li; Gui-Peng Yang (Marine Environmental Research, 2023)

Climate warming may accelerate apple phenology but lead to divergent dynamics in late-spring frost and poor pollination risks in main apple production regions of China - Xiaoya Ru; Jie Zhou; Kaiyuan Gong; Zhihao He; Zhanwu Dai; Meirong Li; Xinxin Feng; Qiang Yu; Hao Feng; Jianqiang He (European Journal of Agronomy, 2023)

Fungal strain improvement for efficient cellulase production and lignocellulosic biorefinery: Current status and future prospects - Jie Yang; Hou-Ru Yue; Li-Ya Pan; Jia-Xun Feng; Shuai Zhao; Surisa Suwannarangsee; Verawat Champreda; Chen-Guang Liu; Xin-Qing Zhao (Bioresource Technology, 2023)

Exploration of using acoustic vibration technology to non-destructively detect moldy kernels of in-shell hickory nuts (Carya cathayensis Sarg.) - Qing-li Han; Bai-xue Long; Xue-jun Yan; Wu Wang; Feng-ru Liu; Xue Chen; Fei Ma (Computers and Electronics in Agriculture, 2023)

Microplastics in coastal farmed oyster (Crassostrea angulata) shells: Abundance, characteristics, and diversity - Chih-Feng Chen; Yun-Ru Ju; Yee Cheng Lim; Ming-Huang Wang; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Metabolomic profiling of Panax ginseng in response to Fusarium solani infection - Guijia Zhao; Shuyang Xing; Yang Wang; Xu Yang; Ru Sun; Lin Feng; Jifeng Wang; Tianxia Sun; Wenhui Lian; Yu Zhao (Physiological and Molecular Plant Pathology, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

Identifying potential toxic organic substances in leachates from tire wear particles and their mechanisms of toxicity to Scenedesmus obliquus - Jie-Ru Jiang; Zhi-Feng Chen; Xiao-Liang Liao; Qian-Yi Liu; Jia-Ming Zhou; Shi-Ping Ou; Zongwei Cai (Journal of Hazardous Materials, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

(±)-Sarcanan A, a pair of new enantiomeric dihydrobenzofuran neolignans from the aerial parts of Sarcandra glabra - Ju Liu; Qi-yin Wen; Hong-ru Tian; Bing-jin-feng Zhan; Long-ping Zhu; De-po Yang; Zhi-min Zhao (Natural Product Research, 2023)

Comprehensive assessment of metals and organic pollutants in pelagic fishing port sediments - Chih-Feng Chen; Shu-Hui Lee; Yun-Ru Ju; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

Anammox bacteria adapt to long-term light irradiation in photogranules - Lingrui Kong; Ru Zheng; Yiming Feng; Wenran Du; Chen Xie; Yuanqi Gu; Sitong Liu (Water Research, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Pollinium development and sporoderm structure of Dendrobium officinale - Yi Feng Cui; Ting Zhou; Ya Ru Wei; De Quan Wang; Wen Yu Liang; Shu Juan Yang (Flora, 2023)

A PKM2 inhibitor induces apoptosis and autophagy through JAK2 in human oral squamous cell carcinoma cells - Jing-Ru Weng; Balraj Gopula; Po-Chen Chu; Jing-Lan Hu; Chia-Hsien Feng (Chemico-Biological Interactions, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Ye-Hui Chen; Yi-Cheng Xu; Ting-Ting Lin; Hang Chen; Ru-Nan Dong; Feng-Ping Cai; Zhi-Bin Ke; Jia-Yin Chen; Yong Wei; Qing-Shui Zheng; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

A novel pollution index to assess the metal bioavailability and ecological risks in sediments - Chih-Feng Chen; Yee Cheng Lim; Yun-Ru Ju; Frank Paolo Jay B. Albarico; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Polysaccharides from the hard shells of Juglans regia L. modulate intestinal function and gut microbiota in vivo - Xiaoyu Li; Siying An; Zhen Luo; Peng Zhou; Lu Wang; Ru Feng (Food Chemistry, 2023)

4-OI ameliorates bleomycin-induced pulmonary fibrosis by activating Nrf2 and suppressing macrophage-mediated epithelial-mesenchymal transition - Ya-xian Wu; Ya-ru Zhang; Feng-juan Jiang; Shuai He; Yan-li Zhang; Dan Chen; Ying Tong; Yun-juan Nie; Qing-feng Pang (Inflammation Research, 2023)

NOS2/miR-493-5p Signaling Regulates in the LPS-Induced Inflammatory Response in the RAW264.7 Cells - Xiaofei Li; Yongrui Yang; Nihong Lu; Feng Luo; Ru Fan; Niancai Peng (Biochemical Genetics, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Renewable pickering emulsion system based on bifunctional materials for highly efficient fuel oil desulfurization without stirring - Shuai-Yong Dou; Jia-Yu An; Yan-Ru Feng; Kang Liu; Xuan Wang; Bo-Wen Zhang; Jing-Xuan Zhang; Er-Hong Duan; Ai-Bin Kang (Fuel, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Methylated Chromenoquinoline as a Novel Nucleus Fluorescent Probe for Nucleic Acid Imaging - Zhi-Hao Zhang; Qing Yu; Gang Zhang; Hai-Yan Peng; Ru Sun; Yu-Jie Xu; Jian-Feng Ge (Journal of Fluorescence, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Interaction investigation of three forest waste biochars and CaO in the process of Ca-L/CARBONOx - Jin-gang Li; Zi-ru Xiong; Li-hui Zhang; Feng Duan (Fuel, 2023)

Genomic vulnerability to climate change in Quercus acutissima , a dominant tree species in East Asian deciduous forests - Shuai Yuan; Yong Shi; Biao‐Feng Zhou; Yi‐Ye Liang; Xue‐Yan Chen; Qing‐Qing An; Yan‐Ru Fan; Zhao Shen; Pär K. Ingvarsson; Baosheng Wang (Molecular Ecology, 2023)
Understanding the evolutionary processes that shape the landscape of genetic variation and influence the response of species to future climate change is critical for biodiversity conservation. Here, we sampled 27 populations across the distribution range of a dominant forest tree, Quercus acutissima , in East Asia, and applied genome‐wide analyses to track the evolutionary history and predict the fate of populations under future climate. We found two genetic groups (East and West) in Q. acutissima that diverged during Pliocene. We also found a heterogeneous landscape of genomic variation in this species, which may have been shaped by population demography and linked selections. Using genotype‐environment association analyses, we identified climate‐associated SNPs in a diverse set of genes and functional categories, indicating a model of polygenic adaptation in Q. acutissima . We further estimated three genetic offset metrics to quantify genomic vulnerability of this species to climate change due to the complex interplay between local adaptation and migration. We found that marginal populations are under higher risk of local extinction because of future climate change, and may not be able to track suitable habitats to maintain the gene–environment relationships observed under the current climate. We also detected higher reverse genetic offsets in northern China, indicating that genetic variation currently present in the whole range of Q. acutissima may not adapt to future climate conditions in this area. Overall, this study illustrates how evolutionary processes have shaped the landscape of genomic variation, and provides a comprehensive genome‐wide view of climate maladaptation in Q. acutissima .

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Dynamic changes in cell wall-degrading enzymes and physio-biochemistry of ginseng in response to fusarium oxysporum infection - Lin Feng; Guijia Zhao; Ru Sun; Jifeng Wang; Tianxia Sun; Shuyang Xing; Wenhui Lian; Yu Zhao (European Journal of Plant Pathology, 2023)

Use of nanoparticle-coated bacteria for the bioremediation of organic pollution: A mini review - Jin-Ru Feng; Qing-Xin Deng; Shang-Kun Han; Hong-Gang Ni (Chemosphere, 2023)

The preparation of Co/γ-Al2O3 and treatment of cartap pesticide wastewater by microwave catalytic oxidation - Jia Ru Dai; Kai Xuan Liu; Fang Lian; Xue Peng Tian; Yu Feng Zhang (Journal of Water Process Engineering, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

Plant growth-promoting properties of the phosphate-solubilizing red yeast Rhodosporidium paludigenum - Yi-Ru Chen; Chih-Yen Kuo; Shih-Feng Fu; Jui-Yu Chou (World Journal of Microbiology and Biotechnology, 2023)
Phosphorus (P) is one of the essential elements that are necessary for plant development and growth. However, the availability of soluble forms of P for plants in the soils is limited, because a large proportion of it is bound to soil constituents. Thus, the concentration of P available to plants at any time is very low and, moreover, its availability depends on the soil pH. As a solution, phosphate-solubilizing microorganisms (PSMs) are employed that render inorganic P available to plants in soluble form. Thus far, research into PSMs has been insufficient, and only few such organisms have been considered for exploitation as microbial fertilizer strains. The characteristics of plant growth promotion with the plant-PSMs coculture system remain to be elucidated. In the current study, we report on the isolate Rhodosporidium paludigenum JYC100 that exhibits good performance for solubilizing calcium phosphate. We found that it can be regulated by the amount of soluble phosphate. Furthermore, R . paludigenum JYC100 promotes plant growth under specific conditions (P deficiency, but with insoluble phosphate) in different media and soil pots. In contrast, the yeast Aureobasidium pullulans JYC104 exhibited weak phosphate-solubilizing capacities and no plant growth-promoting ability. Compared to control plants, the biomass, shoot height, and cellular inorganic P content of plants increased in plants cocultivated with R . paludigenum JYC100. In addition, histochemical GUS and qRT-PCR assays of phosphate starvation-induced (PSI) genes showed that the transcript levels of these PSI genes are decreased in the plants cocultured with R . paludigenum JYC100. These findings reflect the unique ability of R . paludigenum JYC100 to convert insoluble P compounds to plant-available P, thereby leading to growth promotion. Our study results highlight the use of yeasts as potential substitutes for inorganic phosphate fertilizers to meet the P demands of plants, which may eventually improve yields in sustainable agricultures.

Contribution of Tibetan Plateau ecosystems to local and remote precipitation through moisture recycling - Yan Li; Ru Xu; Kun Yang; Yanxu Liu; Shuai Wang; Sha Zhou; Zhao Yang; Xiaoming Feng; Chunyang He; Zhengjie Xu; Wenwu Zhao (Global Change Biology, 2023)
The ecosystems of the Tibetan Plateau (TP) provide multiple important ecosystem services that benefit both local populations and those beyond, such as through climate regulation services on precipitation for East Asia and China. However, the precipitation regulation service of the TP ecosystems for supplying moisture and maintaining precipitation is yet to be evaluated. In this study, we used the moisture recycling framework and a moisture tracking model to quantify the precipitation regulation services of TP ecosystems for their contribution to precipitation. We found TP ecosystems contributed substantially to local and downwind precipitation, with a contribution of 221 mm/year for the TP and neighboring areas through evapotranspiration (ET) (104 mm/year through transpiration), declined to

Efficient microalgal lipid production driven by salt stress and phytohormones synergistically - Zi-Yan Yang; Kai-Xuan Huang; Yu-Ru Zhang; Lei Yang; Jin-Long Zhou; Qiao Yang; Feng Gao (Bioresource Technology, 2023)

Transcriptome‐based analyses of adaptive divergence between two closely related spruce species on the Qinghai–Tibet plateau and adjacent regions - Shuo Feng; Wei Wan; Yang Li; DongLei Wang; Guangpeng Ren; Tao Ma; Dafu Ru (Molecular Ecology, 2023)
Speciation among populations connected by gene flow is driven by adaptation to different environments, but underlying gene–environment associations remain largely unknown. Here, 162 individuals from 32 populations were sampled to obtain 191,648 independent single nucleotide polymorphisms (SNPs) across the genomes of two closely related spruce species, Picea asperata and Picea crassifolia , which occur on the Qinghai–Tibet Plateau and in surrounding regions. Using the SNP data set, genotype–environment associations and demographic modelling were used to examine local adaptation and genetic divergence between these two species. While morphologically similar, the two Picea species were genetically differentiated in multiple analyses. These species diverged despite continuous gene flow, and their initial divergence was dated back to the late Quaternary. The effective population sizes of both species have expanded since their divergence, as confirmed by niche distribution simulations. A total of 6365 genes were associated with the tested environmental variables; of these, 41 were positively selected in P. asperata and were mainly associated with temperature, while 83 were positively selected in P. crassifolia and were primarily associated with precipitation. These results deepen our understanding of the adaptive divergence and demographic histories of these two spruce species and highlight the importance of genomic data in deciphering the environmental selection underlying Quaternary interspecific divergence.

Differences in drought evolution as portrayed for China using various evapotranspiration models and drought indices - Huaijun Wang; Lei Cao; Xinchuan Li; Ru Feng; Peng Zheng (International Journal of Climatology, 2022)
Drought, a slow‐growing natural disaster that affects large areas worldwide, has serious social and economic consequences. There is compelling evidence to suggest that drought will be more prevalent in various regions in the future, due to the impact of climate change. Evapotranspiration is an important drought evolution control factor, and various evapotranspiration models show different drought evolution trends. In the study described here, meteorological data from 840 Chinese weather stations, for 1960–2018, were used to estimate potential evapotranspiration (PET), using the Thomthwaite (TH), Hargreaves (HG), Priestley–Taylor (PT), Penman and Penman–Monteith (PM) models. We then compared various drought indices (the standardized precipitation index [SPI], the standardized precipitation evapotranspiration index [SPEI], and the Palmer drought severity index [PDSI]), calculated using inputs from the five evapotranspiration models. The results showed that (a) evapotranspiration means and trends, as estimated by the five PET models, were significantly different, with Penman giving the highest estimate while TH the lowest. Differences between the PET model outcomes reduced under climate warming scenarios; (b) significantly different evapotranspiration models and drought indices can give rise to varied results, with the climate becoming wetter under the Penman and PM models (especially in western northwest China and eastern south China), and drier under the TH model; (c) the different drought forecasts obtained using the evapotranspiration models decreased with increasing precipitation, for all regions; (d) the SPEI is more suitable for drought monitoring compared with PDSI due to the higher sensitive to the choice of evapotranspiration model of SPEI; and (e) SPEI‐PM and SPEI‐Penman is the best drought indices in all regions. SPEI‐PT and SPEI‐HG can be applied in regions with relatively abundant precipitation (northern north China, southern north China, eastern south China, western south China, and Tibetan Plateau), and SPEI‐PM and SPEI‐Penman can be suitable for drought monitoring in arid and semi‐arid regions (western northwest China and eastern northwest China). The results presented herein are expected to aid in the selection of a proper drought index for disaster assessment.

Lipocalin-2-Mediated Insufficient Oligodendrocyte Progenitor Cell Remyelination for White Matter Injury After Subarachnoid Hemorrhage via SCL22A17 Receptor/Early Growth Response Protein 1 Signaling - Qiang Li; Xufang Ru; Yang Yang; Hengli Zhao; Jie Qu; Weixiang Chen; Pengyu Pan; Huaizhen Ruan; Chaojun Li; Yujie Chen; Hua Feng (Neuroscience Bulletin, 2022)
Insufficient remyelination due to impaired oligodendrocyte precursor cell (OPC) differentiation and maturation is strongly associated with irreversible white matter injury (WMI) and neurological deficits. We analyzed whole transcriptome expression to elucidate the potential role and underlying mechanism of action of lipocalin-2 (LCN2) in OPC differentiation and WMI and identified the receptor SCL22A17 and downstream transcription factor early growth response protein 1 (EGR1) as the key signals contributing to LCN2-mediated insufficient OPC remyelination. In LCN-knockdown and OPC EGR1 conditional-knockout mice, we discovered enhanced OPC differentiation in developing and injured white matter (WM); consistent with this, the specific inactivation of LCN2/SCl22A17/EGR1 signaling promoted remyelination and neurological recovery in both atypical, acute WMI due to subarachnoid hemorrhage and typical, chronic WMI due to multiple sclerosis. This potentially represents a novel strategy to enhance differentiation and remyelination in patients with white matter injury.

PITPNC1 promotes the thermogenesis of brown adipose tissue under acute cold exposure - Guoqing Tang; Chengxin Ma; Liangkui Li; Shaoyan Zhang; Fengsheng Li; Jin Wu; Yesheng Yin; Qing Zhu; Yan Liang; Ru Wang; He Huang; Tong-Jin Zhao; et al. (Science China Life Sciences, 2022)
Brown adipose tissue (BAT) plays an essential role in non-shivering thermogenesis. The phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) is identified as a lipid transporter that reciprocally transfers phospholipids between intracellular membrane structures. However, the physiological significance of PITPNC1 and its regulatory mechanism remain unclear. Here, we demonstrate that PITPNC1 is a key player in thermogenesis of BAT. While Pitpnc1 −/− mice do not differ with wildtype mice in body weight and insulin sensitivity on either chow or high-fat diet, they develop hypothermia when subjected to acute cold exposure at 4°C. The Pitpnc1 −/− brown adipocytes exhibit defective β-oxidation and abnormal thermogenesis-related metabolism pathways in mitochondria. The deficiency of lipid mobilization in Pitpnc1 −/− brown adipocytes might be the result of excessive accumulation of phosphatidylcholine and a reduction of phosphatidic acid. Our findings have uncovered significant roles of PITPNC1 in mitochondrial phospholipid homeostasis and BAT thermogenesis.

Progressive Failure Characterization of Sandstone from Yingjinshan Area in Qinghai-Tibet Plateau - Xinzhong Wang; Heping Xie; Ru Zhang; Guangze Zhang; Zhengxuan Xu; Jianhui Deng; Dong Wang; Cunbao Li; Gan Feng; Zetian Zhang; Li Ren (Rock Mechanics and Rock Engineering, 2022)

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Strength and deformation behavior of columnar jointed rock masses under different confining pressures - Zhi-nan Lin; Hai-feng Long; Wei-ya Xu; Ru-bin Wang; Shi-hong Feng (Arabian Journal of Geosciences, 2022)

Stachybotranes A–D, phenylspirodrimanes from the wetland fungus Stachybotrys chartarum with cytotoxic activities - Yan-Ru Bao; Han-Lin Feng; Xin-Sheng Yao (Natural Product Research, 2022)

A 2D CSIA-based math method to quantify degradation rate by C–H bond breaking - Jin-Ru Feng; Hong-Gang Ni (Environmental Geochemistry and Health, 2022)

Energy characteristics and micro-cracking behaviors of deep slate rock under triaxial loadings - Anlin Zhang; Tao Feng; Liangwen Jiang; Dong Wang; Zhewei Wang; Ru Zhang; Gan Feng; Zhilong Zhang; Jianhui Deng; Li Ren (Acta Geophysica, 2022)

Spatiotemporal variations of seasonal temperature at different percentiles in the three provinces of northeast China from 1961 to 2019 - Yaxue Yang; Huixiao Wang; Changming Liu; Ru Feng; Yu Wang; Hongfang Li (International Journal of Climatology, 2022)
The three provinces of northeast China (NEPs) were one of the major grain producing areas in China and has undergone significant climate warming during past decades. However, nowadays researches on climate warming mostly focused on variations of mean temperature or temperature extremes, which missed much information in the other parts of temperature. Therefore, taken NEPs as study area, variations of maximum temperature (Tmax), minimum temperature (Tmin) and diurnal temperature range (DTR) at every 10% percentile from 1961 to 2019 in NEPs were analysed at seasonal scale. The abrupt changes and decadal shifts of Tmax, Tmin and DTR at different percentiles were further highlighted. Results show that (a) for either regional average or station cases, fluctuations of daily Tmax and daily Tmin both decreased in spring and winter, but increased in autumn. In summer, fluctuations of daily Tmin decreased while those of daily Tmax increased. (b) Spatially, Tmax heated up more in south of NEPs at lower percentiles, and in northwest of NEPs at higher percentiles in spring, summer and winter. Tmin and DTR overall showed consistent spatial differences that changes in north and northwest of NEPs were with greater magnitudes. (c) In spring and winter, the higher Tmax/Tmin had earlier abrupt changes than lower Tmax/Tmin, while in summer and autumn, the abrupt changes occurred earlier for lower Tmax/Tmin. (d) In winter, overwhelming positive shifts were significant before 2000, but turned negative after 2000. In summer, Tmax heated up quickly since 1990s and Tmin since 1980s. Shifts in spring and autumn varied during different periods and generally presented alternative warming at higher and lower percentiles. The research can help better depict the warming patterns and figure out the detailed warming procedures in NEPs, which is a strong supplement for current climate change research.

miR-211-3p enhances induction chemotherapy insensitivity by upregulating CSF2/CCL20/TNF signaling in hypopharyngeal squamous cell carcinoma - Lingwa Wang; Ru Wang; Tianqiao Huang; Yifan Yang; Ling Feng; Jugao Fang (Molecular Biology Reports, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

First report of Cytospora chrysosperma causing canker on staghorn sumac in China - Zhe Wang; Hai-ting Hao; Shuai-shuai Sha; Sha-sha Peng; Xin-ru Zhang; Lan Wang; Hong-zu Feng (Journal of Plant Pathology, 2022)

Imatinib-induced hepatotoxicity via oxidative stress and activation of NLRP3 inflammasome: an in vitro and in vivo study - Feng-Ru Huang; Wen-Tong Fang; Zi-Ping Cheng; Ye Shen; Dun-Jian Wang; Yong-Qing Wang; Lu-Ning Sun (Archives of Toxicology, 2022)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Expression of the SPL-like gene LaSPL9 in Japanese larch (Larix leptolepis) is regulated by miR156 during somatic embryogenesis - Li-feng Zhang; Yan-ru Fan; Qian Lan; Li-wang Qi; Su-ying Han (Trees, 2021)

Recent progress of oridonin and its derivatives for cancer therapy and drug resistance - Yong-Feng Guan; Xiu-Juan Liu; Xiao-Jing Pang; Wen-Bo Liu; Guang -Xi Yu; Yin -Ru Li; Yan-Bing Zhang; Jian Song; Sai-Yang Zhang (Medicinal Chemistry Research, 2021)

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

Prediction of Metabolic Disorders Using NMR-Based Metabolomics: The Shanghai Changfeng Study - Qi Wu; Qing-xia Huang; Hai-luan Zeng; Shuai Ma; Huan-dong Lin; Ming-feng Xia; Hui-ru Tang; Xin Gao (Phenomics, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

A modified method to calculate dual-isotope slopes for the natural attenuation of organic pollutants in the environment - Jin-Ru Feng; Hong-Gang Ni (Environmental Science and Pollution Research, 2021)

Double Weighted Sparse Nonnegative Tensor Factorization for Hyperspectral Unmixing - Heng-Chao Li; Shuang Liu; Xin-Ru Feng; Rui Wang; Yong-Jian Sun (International Journal of Remote Sensing, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

To the light side: molecular diversity and morphology of stomatopod larvae and juveniles (Crustacea: Malacostraca: Stomatopoda) from crustose coralline algal reefs in Taiwan - Kingsley J. H. Wong; Yao-Feng Tsao; Pei-Chen Tsai; Wei-Peng Hsieh; Han-Ru Li; Ryuji J. Machida; Benny K. K. Chan (Marine Biodiversity, 2021)

Early-Life Multiple Sevoflurane Exposures Alleviate Long-term Anxiety-Like Behaviors in Mice via the proBDNF/ERK Pathway - Ru-Yi Luo; Cong Luo; Feng Zhong; Wei-Yun Shen; Hui Li; Yan-Ling Zhang; Ru-Ping Dai (Molecular Neurobiology, 2021)

A new cyclic peptide from the fibrous root of Pseudostellaria heterophylla - Xiao-fei Zhao; Qian Zhang; Han-tao Zhao; Yan-da Zhang; Han-ru Liu; Lu-jiang Yuan; Qian-feng Chen (Natural Product Research, 2020)

Application and Progress of Reinforcement Technology for Chinese Ancient Buildings with Wood Structure - Ru-yuan Yang; You-fu Sun; Xiao-feng Zhang (Geotechnical and Geological Engineering, 2020)

Functional connectivity changes of nucleus Accumbens Shell portion in left mesial temporal lobe epilepsy patients - Ru Yang; Xixi Zhao; Jun Liu; Xufeng Yao; Feng Hou; Yikai Xu; Qianjin Feng (Brain Imaging and Behavior, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Multiplex RT–PCR Assay for the Simultaneous Detection and Identification of Five Sugarcane Viruses - Xiao-Yan Feng; Wen-Zhi Wang; Lin-Bo Shen; Jun-Gang Wang; Guo-Ru Xiong; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Pasture degradation impact on soil carbon and nitrogen fractions of alpine meadow in a Tibetan permafrost region - Zi-Qiang Yuan; Qing-Bai Wu; Xin Song; Xiao-Jin Jiang; Si-Ru Gao; Qing-Feng Wang; Guo-Yu Li (Journal of Soils and Sediments, 2020)

Occurrence and distribution of priority pharmaceuticals in the Yellow River and the Huai River in Henan, China - Jinglan Feng; Qi Liu; Xiangli Ru; Nannan Xi; Jianhui Sun (Environmental Science and Pollution Research, 2020)

Taxonomy of the yeast genus Vanderwaltozyma and proposal of Vanderwaltozyma meishanica sp. nov., Vanderwaltozyma huisunica sp. nov., and Vanderwaltozyma molinica sp. nov. - Chin-Feng Chang; Yi-Ru Liu; Gennadi I. Naumov; Elena S. Naumova; Ching-Fu Lee (Antonie van Leeuwenhoek, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Comprehensive transcriptome analysis of faba bean in response to vernalization - Bei Gao; Xiao-Chun Bian; Feng Yang; Mo-Xian Chen; Debatosh Das; Xiu-Ru Zhu; Yong Jiang; Jianhua Zhang; Yun-Ying Cao; Chun-Fang Wu (Planta, 2020)

Tumor promoting effects of glucagon receptor: a promising biomarker of papillary thyroid carcinoma via regulating EMT and P38/ERK pathways - Hong-Chun Jiang; Xiang-Ru Chen; Hai-Feng Sun; Yuan-Wen Nie (Human Cell, 2020)

Removal of formaldehyde from the air with a suspended growth bioreactor - Ru Wang; Xuemei Li; Yong Feng; Faheem Tariq; Kunzhi Li; Yulin Wei; Jianhua Chen; Ciqing Jiang; Limei Tian; Yongqin Geng; Enming Miao; Chengming Zhang; et al. (International Journal of Environmental Research, 2019)

An integrative assessment to determine the sediment toxicity of Kaohsiung Harbor in Taiwan: combining chemical analysis and cytotoxicity assay - Yun-Ru Ju; Chih-Feng Chen; Chiu-Wen Chen; Mei-Ling Tsai; Jia-Ching Wu; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Effect of metals on zooplankton abundance and distribution in the coast of southwestern Taiwan - Yun-Ru Ju; Wen-Tseng Lo; Chih-Feng Chen; Chiu-Wen Chen; Zhi-Ling Huang; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Mixed phase nano–CdS supported on activated biomass carbon as efficient visible light–driven photocatalysts - Feng-Ying Cai; Yu-Qing Zhang; Jun-Tao Wang; Jun-Ru Zhou; Hai-Lei Cao; Jian Lü (Environmental Science and Pollution Research, 2019)

Cloning and characterization of terpene synthase genes from Taiwan cherry - Kuan-Feng Huang; Chi-Hsiang Wen; Yi-Ru Lee; Fang-Hua Chu (Tree Genetics & Genomes, 2019)

Thalamocortical dysconnectivity in premenstrual syndrome - Peng Liu; Ying Wei; Hai Liao; Yingying Fan; Ru Li; Nana Feng; Gaoxiong Duan; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2019)

Spatial distribution and ecological risk assessment of sediment metals in a highly industrialized coastal zone southwestern Taiwan - Chiu-Wen Chen; Yee Cheng Lim; Chih-Feng Chen; Yun-Ru Ju; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Triterpenoids, megastigmanes and hydroxycinnamic acid derivatives from Anisomeles indica - Quan-Wen Liu; Cai-Hua Chen; Xiao-Feng Wang; Kun Jiang; Shi-Jin Qu; Yi-Ru Dai; Chang-Heng Tan (Natural Product Research, 2019)

LaMIR166a-mediated auxin biosynthesis and signalling affect somatic embryogenesis in Larix leptolepis - Zhe-Xin Li; Yan-Ru Fan; Shao-Fei Dang; Wan-Feng Li; Li-Wang Qi; Su-ying Han (Molecular Genetics and Genomics, 2018)

Physiological Concentration of Prostaglandin E2 Exerts Anti-inflammatory Effects by Inhibiting Microglial Production of Superoxide Through a Novel Pathway - Shih-Heng Chen; Yueh-Feng Sung; Esteban A. Oyarzabal; Yu-Mei Tan; Jeremy Leonard; Mingri Guo; Shuo Li; Qingshan Wang; Chun-Hsien Chu; Shiou-Lan Chen; Ru-Band Lu; Jau-Shyong Hong (Molecular Neurobiology, 2018)

The complete chloroplast genome sequence of an endangered species, Dendrobium pendulum Roxb. (Orchidaceae) - Li-Ru Wang; Shi-Qiang Wang; Jun-Feng Niu; Shang-Ping Wang; Zhe-Zhi Wang (Conservation Genetics Resources, 2018)

Combined prednisone and levothyroxine improve treatment of severe thrombocytopenia in hepatitis B with compensatory cirrhosis accompanied by subclinical and overt hypothyroidism - Jing Xue; Ru Feng; Haixia Fu; Qian Jiang; Hao Jiang; Jing Lu; Hui Liu; Jingwen Wang; Ting Niu; Xin Wang; Yandi Xie; Hao Wang; et al. (Science China Life Sciences, 2018)

Application of Phragmites australis to remove phenol from aqueous solutions by chemical activation in batch and fixed-bed columns - Sheng-Li Shi; Jun-Ping Lv; Qi Liu; Fang-Ru Nan; Xiao-Yan Jiao; Jia Feng; Shu-Lian Xie (Environmental Science and Pollution Research, 2018)

Luteolin alleviates cardiac ischemia/reperfusion injury in the hypercholesterolemic rat via activating Akt/Nrf2 signaling - Jin-Ting Yang; Jue Wang; Xin-Ru Zhou; Chi Xiao; Yang-Yun Lou; Li-Hui Tang; Feng-Jiang Zhang; Ling-Bo Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Whole-genome sequence and genome annotation of Xanthomonas citri pv. mangiferaeindicae, causal agent of bacterial black spot on Mangifera indica - Feng Liu; Xiong-chang Ou; Ru-lin Zhan (Archives of Microbiology, 2018)

Scopuquinolone B, a new monoterpenoid dihydroquinolin-2(1 H )-one isolated from the coral-derived Scopulariopsis sp. fungus - Xiao-Feng Mou; Xin Liu; Ru-Fang Xu; Mei-Yan Wei; Yao-Wei Fang; Chang-Lun Shao (Natural Product Research, 2018)

Spatial and temporal variations in extreme temperature in Central Asia - Ru Feng; Ruide Yu; Hongwei Zheng; Miao Gan (International Journal of Climatology, 2018)
Central Asia, a typical arid and semi‐arid area, is very sensitive to climate change and is projected to undergo vigorous warming trend in future. However, it is still unclear how extreme temperatures have changed. Therefore, using the daily maximum and minimum temperatures collected from 108 stations in the study area from 1981 to 2015, the spatial–temporal variations in extreme temperature in Central Asia were analysed on both annual and seasonal scales based on 11 indices from The Expert Team on Climate Change Detection and Indices. Results show that: (1) from 1981 to 2015, all extreme temperature values exhibited increasing trends on an annual scale, but maximum temperature (TMAX) increased faster than the minimum temperature (TMIN), leading to an overall increase in the diurnal temperature range (DTR). Most of the stations in Central Asia, except for those in Xinjiang (China), exhibited an increasing trend in DTR, while most of the stations in Xinjiang (China) exhibited reversely significant decreasing trends. (2) TMAX, TMIN and DTR increased significantly, mainly during spring and summer. The trends of most warm extreme indices (warm days, warm nights and warmest days) indicate that the warming mainly occurred in spring, while most cold extreme indices (cool days, cool nights and coldest nights) exhibited significant warming trends in autumn. Dominant warming during spring and autumn can lead to longer summers, which may further accelerate the frequencies and magnitudes of temperature extremes. (3) Additionally, TMAX, TMIN and the percentile‐based warm indices all exhibited significant increasing trends from southwestern Central Asia (Turkmenistan) to eastern Central Asia (Xinjiang (China)) via the Tianshan Mountains. Although the percentile‐based cold indices showed decreasing trends in this region, they were too minor to offset the overall warming trend. With longer summers, stronger and more prolonged melting seasons were detected in the mountains of Central Asia.

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1 - Yu Zhou; Jia Xu; Shi-Kang Zhu; Qing-Feng Meng; Zhi-Xiong Lin; Ru Chen; Ai-Dong Qian (Archives of Virology, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

New phenolic acids from Salvia yunnanensis C.H.Wright - Yun Yu; Yin-ru Wang; Zhen-huan Dong; Wei Li; Shu-Ming Li; Xue-feng Huang (Natural Product Research, 2017)

Influence of Rapeseed Cake on Iron Plaque Formation and Cd Uptake by Rice (Oryza sativa L.) Seedlings Exposed to Excess Cd - Wen-Tao Yang; Hang Zhou; Jiao-Feng Gu; Qing-ru Zeng; Bo-Han Liao (Bulletin of Environmental Contamination and Toxicology, 2017)

Clinical Significance of REM Sleep Behavior Disorders and Other Non-motor Symptoms of Parkinsonism - Hong Jin; Jin-Ru Zhang; Yun Shen; Chun-Feng Liu (Neuroscience Bulletin, 2017)

Effects of xeric shrubs on soil microbial communities in a desert in northern China - Yanfei Sun; Yuqing Zhang; Wei Feng; Shugao Qin; Zhen Liu; Yuxuan Bai; Ru Yan; Keyu Fa (Plant and Soil, 2017)

The pharmacological activities and mechanisms of artemisinin and its derivatives: a systematic review - Yi-Fei Dai; Wei-Wei Zhou; Jing Meng; Xin-Liang Du; Yun-Peng Sui; Li Dai; Peng-Qian Wang; Hai-Ru Huo; Feng Sui (Medicinal Chemistry Research, 2017)

Reversible Absorption and Emission Responses of Nile Blue and Azure A Derivatives in Extreme Acidic and Basic Conditions - Xiu-Li Wang; Ru Sun; Wei-Jin Zhu; Xin-Long Sha; Jian-Feng Ge (Journal of Fluorescence, 2017)

Quantification of 3D macropore networks in forest soils in Touzhai valley (Yunnan, China) using X-ray computed tomography and image analysis - Jia-ming Zhang; Ze-min Xu; Feng Li; Ru-ji Hou; Zhe Ren (Journal of Mountain Science, 2017)

Genomewide association study for seeding emergence and tiller number using SNP markers in an elite winter wheat population - GUANG FENG CHEN; RU GANG WU; DONG MEI LI; HAI XIA YU; ZHIYING DENG; JI CHUN TIAN (Journal of Genetics, 2017)

A Selective Colorimetric and Turn-on Fluorescent Chemosensor for Hg2+ in Aqueous Solution - Yi-Ru Chiou; Chin-Feng Wan; An-Tai Wu (Journal of Fluorescence, 2017)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Peripheral Blood MicroRNA Expression Profiles in Alzheimer’s Disease: Screening, Validation, Association with Clinical Phenotype and Implications for Molecular Mechanism - Ru-Jing Ren; Yong-Fang Zhang; Eric B. Dammer; Yi Zhou; Li-ling Wang; Xiao-Hong Liu; Bei-Lei Feng; Guo-Xin Jiang; Sheng-Di Chen; Gang Wang; Qi Cheng (Molecular Neurobiology, 2016)

Impacts of rapeseed dregs on Cd availability in contaminated acid soil and Cd translocation and accumulation in rice plants - Wen-Tao Yang; Jiao-Feng Gu; Jia-Ling Zou; Hang Zhou; Qing-Ru Zeng; Bo-Han Liao (Environmental Science and Pollution Research, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

The regulatory role of silicon on carbohydrate metabolism in Cucumis sativus L. under salt stress - Yongxing Zhu; Jia Guo; Ru Feng; Jianhua Jia; Weihua Han; Haijun Gong (Plant and Soil, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

Silicon reduces long-term cadmium toxicities in potted garlic plants - Yichao Wang; Yanhong Hu; Yaoke Duan; Ru Feng; Haijun Gong (Acta Physiologiae Plantarum, 2016)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Vertical profile, source apportionment, and toxicity of PAHs in sediment cores of a wharf near the coal-based steel refining industrial zone in Kaohsiung, Taiwan - Chih-Feng Chen; Chiu-Wen Chen; Yun-Ru Ju; Cheng-Di Dong (Environmental Science and Pollution Research, 2016)

Cloning, molecular characterization and functional analysis of a putative R2R3-MYB transcription factor of the phenolic acid biosynthetic pathway in S. miltiorrhiza Bge. f. alba - Gangping Hao; Xingyu Jiang; Lei Feng; Ru Tao; Yanling Li; Luqi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Di-(2-ethylhexyl) phthalate accelerates atherosclerosis in apolipoprotein E-deficient mice - Jin-Feng Zhao; Sheng-Huang Hsiao; Ming-Hua Hsu; Kuan-Chuan Pao; Yu Ru Kou; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

An efficient SAR edge detector with a lower false positive rate - Qian-Ru Wei; Da-Zheng Feng (International Journal of Remote Sensing, 2015)

Changes in root morphology and physiology to limited phosphorus and moisture in a locally-selected cultivar and an introduced cultivar of Medicago sativa L. growing in alkaline soil - Jing-Wei Fan; Yan-Lei Du; Neil C. Turner; Bing-Ru Wang; Yan Fang; Yue Xi; Xiao-Ran Guo; Feng-Min Li (Plant and Soil, 2015)

Effect of microRNA-203 on tumor growth in human hypopharyngeal squamous cell carcinoma - Ru Wang; Jugao Fang; Hongzhi Ma; Lin Feng; Meng Lian; Fan Yang; Haizhou Wang; Qi Wang; Xiaohong Chen (Molecular and Cellular Biochemistry, 2015)

Coronary Revascularization Improves QT Dispersion in Patients with Chronic Coronary Artery Total Occlusion - Feng Zhang; Xiaojian Zhang; Xin Zhang; Bo Chen; Yukun Liu; Wen-wei Yue; Ru-yi Jia (Cell Biochemistry and Biophysics, 2015)

Two new triterpenoids from Nauclea officinalis - Hai-Yang Wang; Ke Liu; Ru-Xia Wang; San-Hai Qin; Feng-Ling Wang; Jing-Yong Sun (Natural Product Research, 2015)

Annual thawing and freezing indices changes in the China Tianshan Mountains - Feng-qing Jiang; Abudu-waili Jilili; Shao-ping Wang; Ru-ji Hu; Xiao-lan Li (Regional Environmental Change, 2015)

Rock Burst Intensity Classification Based on the Radiated Energy with Damage Intensity at Jinping II Hydropower Station, China - Bing-Rui Chen; Xia-Ting Feng; Qing-Peng Li; Ru-Zhou Luo; Shaojun Li (Rock Mechanics and Rock Engineering, 2015)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

Gene order rearrangement of the M gene in the rabies virus leads to slower replication - Xian-Feng Yang; Jiao-Jiao Peng; Hong-Ru Liang; You-Tian Yang; Yi-Fei Wang; Xiao-Wei Wu; Jiao-Jiao Pan; Yong-Wen Luo; Xiao-Feng Guo (VirusDisease, 2014)

The Attenuation of Lung Ischemia Reperfusion Injury by Oxymatrine - Bing Zhu; Jian-Ru Yang; Shi-Feng Chen; Yue Quan Jiang (Cell Biochemistry and Biophysics, 2014)

Evaluation of Angiogenesis in Non-small Cell Lung Carcinoma by CD34 Immunohistochemistry - Zhu Bing; Yang Jian-ru; Jiang Yao-quan; Chen Shi-feng (Cell Biochemistry and Biophysics, 2014)

Gene Therapy of Lung Adenocarcinoma using Herpes Virus Expressing a Fusogenic Membrane Glycoprotein - Bing Zhu; Jian-ru Yang; Yue-quan Jiang; Shi-feng Chen; Xin-ping Fu (Cell Biochemistry and Biophysics, 2014)

Establishment of a Spinal Cord Injury Model in Adult Rats by an Electrocircuit-Controlled Impacting Device and its Pathological Observations - Yun Wang; Chun-feng Liu; Qi-ping Wang; Heng Gao; Han-rong Na; Ru-tong Yu (Cell Biochemistry and Biophysics, 2014)

Prefrontal Control of Cerebellum-Dependent Associative Motor Learning - Hao Chen; Li Yang; Yan Xu; Guang-yan Wu; Juan Yao; Jun Zhang; Zhi-ru Zhu; Zhi-an Hu; Jian-feng Sui; Bo Hu (The Cerebellum, 2014)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Comparison of the dissipation behaviour of three neonicotinoid insecticides in tea - Ru-Yan Hou; Jin-Feng Hu; Xiao-San Qian; Ting Su; Xiao-Hui Wang; Xiu-Xia Zhao; Xiao-Chun Wan (Food Additives & Contaminants: Part A, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

A new sesquiterpene lactone from Sarcandra glabra - Xiao-Ru Hu; Hai-Feng Wu; Xiao-Po Zhang; Jun-Shan Yang; Zhong Dai; Rui-Chao Lin; Xu-Dong Xu (Natural Product Research, 2013)

Functional analysis of BT4 of Arabidopsis thaliana in resistance against Botrytis cinerea - Cong-Cong Hao; Jiao Jia; Zhan Chen; Ji-Hong Xing; Qiao-Yun Weng; Feng-Ru Wang; Jin-Gao Dong; Jian-Min Han (Australasian Plant Pathology, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Oyster shell reduces PAHs and particulate matter from incense burning - Chi-Ru Yang; Tzu-Hsing Ko; Yuan-Chung Lin; Suen-Zone Lee; Yih-Feng Chang; Hsin-Ta Hsueh (Environmental Chemistry Letters, 2013)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Trends of precipitation extremes during 1960–2008 in Xinjiang, the Northwest China - Feng-qing Jiang; Ru-Ji Hu; Shao-Ping Wang; Yan-Wei Zhang; Li Tong (Theoretical and Applied Climatology, 2013)

Sequence and phylogenetic analysis of H7N3 avian influenza viruses isolated from poultry in China in 2011 - Wu Hai-bo; Lu Ru-feng; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Xu Li-hua; Wu Nan-ping; Guo Chao-tan (Archives of Virology, 2012)

Demography and speciation history of the homoploid hybrid pine Pinus densata on the Tibetan Plateau - JIE GAO; BAOSHENG WANG; JIAN‐FENG MAO; PÄR INGVARSSON; QING‐YIN ZENG; XIAO‐RU WANG (Molecular Ecology, 2012)
Pinus densata is an ecologically successful homoploid hybrid that inhabits vast areas of heterogeneous terrain on the south‐eastern Tibetan Plateau as a result of multiple waves of colonization. Its region of origin, route of colonization onto the plateau and the directions of introgression with its parental species have previously been defined, but little is known about the isolation and divergence history of its populations. In this study, we surveyed nucleotide polymorphism over eight nuclear loci in 19 representative populations of P. densata and its parental species. Using this information and coalescence simulations, we assessed the historical changes in its population size, gene flow and divergence in time and space. The results indicate a late Miocene origin for P. densata associated with the recent uplift of south‐eastern Tibet. The subsequent differentiation between geographical regions of this species began in the late Pliocene and was induced by regional topographical changes and Pleistocene glaciations. The ancestral P. densata population had a large effective population size but the central and western populations were established by limited founders, suggesting that there were severe bottlenecks during the westward migration out of the ancestral hybrid zone. After separating from their ancestral populations, population expansion occurred in all geographical regions especially in the western range. Gene flow in P. densata was restricted to geographically neighbouring populations, resulting in significant differentiation between regional groups. The new information on the divergence and demographic history of P. densata reported herein enhances our understanding of its speciation process on the Tibetan Plateau.

Role of ROS/RhoA/PI3K/PKB Signaling in NS1619-Mediated Blood–Tumor Barrier Permeability Increase - Yan-Ting Gu; Yi-Xue Xue; Yan-Feng Wang; Jin-Hui Wang; Qian-Ru ShangGuan; Jia-Xu Zhang; Li-Juan Qin (Journal of Molecular Neuroscience, 2012)

Genetic characterization of subtype H1 avian influenza viruses isolated from live poultry markets in Zhejiang Province, China, in 2011 - Hai-bo Wu; Chao-tan Guo; Ru-feng Lu; Li-hua Xu; En-kang Wo; Jin-biao You; Yi-ting Wang; Qiao-gang Wang; Nan-ping Wu (Virus Genes, 2012)

Characterization of a highly pathogenic H5N1 avian influenza virus isolated from ducks in Eastern China in 2011 - Wu Hai-bo; Guo Chao-tan; Lu Ru-feng; Xu Li-hua; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Wu Nan-ping (Archives of Virology, 2012)

Five novel species of the anamorphic genus Candida in the Cyberlindnera clade isolated from natural substrates in Taiwan - Chin-Feng Chang; Yi-Ru Liu; Shan-Fu Chen; Gennadi I. Naumov; Elena S. Naumova; Ching-Fu Lee (Antonie van Leeuwenhoek, 2012)

Assessment of Recanalization of Chronic Total Occlusions on Left Ventricular Function in Patients With or Without Previous Myocardial Infarction by Real-time Three-Dimensional Echocardiography - Wen-Wei Yue; Feng-Tian Huangfu; Jie Yin; Tao Wang; Guang-Fu Wang; Ru-Yi Jia (Cell Biochemistry and Biophysics, 2012)

Variations and trends of onset, cessation and length of climatic growing season over Xinjiang, NW China - Feng-qing Jiang; Ru-ji Hu; Yan-wei Zhang; Xue-mei Li; Li Tong (Theoretical and Applied Climatology, 2011)

QTL mapping of bio-energy related traits in Sorghum - Yan-an Guan; Hai-lian Wang; Ling Qin; Hua-wen Zhang; Yan-bing Yang; Feng-ju Gao; Ru-yu Li; Hong-gang Wang (Euphytica, 2011)

Infrasound Exposure Induces Apoptosis of Rat Cardiac Myocytes by Regulating the Expression of Apoptosis-Related Proteins - Zhao-Hui Pei; Bao-Ying Chen; Ru Tie; Hai-Feng Zhang; Ge Zhao; Ping Qu; Xiao-Xing Zhu; Miao-Zhang Zhu; Jun Yu (Cardiovascular Toxicology, 2011)

Acute Phase Expression Pattern of ZnTs, LC3, and Beclin-1 in Rat Hippocampus and Its Regulation by 3-Methyladenine Following Recurrent Neonatal Seizures - Hong Ni; Xing Feng; Yong Gong; Lu-yang Tao; Xi-ru Wu (Biological Trace Element Research, 2011)

Colonization of the Tibetan Plateau by the homoploid hybrid pine Pinus densata - BAOSHENG WANG; JIAN‐FENG MAO; JIE GAO; WEI ZHAO; XIAO‐RU WANG (Molecular Ecology, 2011)
Pinus densata is an intriguingly successful homoploid hybrid species that occupies vast areas of the southeastern Tibetan Plateau in which neither of its parental species are present, but the colonization processes involved are poorly understood. To shed light on how this species colonized and became established on the plateau, we surveyed paternally inherited chloroplast (cp) and maternally inherited mitochondrial (mt) DNA variation within and among 54 populations of P. densata and its putative parental species throughout their respective ranges. Strong spatial genetic structure of both cp and mtDNA were detected in P. densata populations. Mitotypes specific to P. densata were likely generated by complex recombination events. A putative ancestral hybrid zone in the northeastern periphery of P. densata was identified, and we propose that the species then colonized the plateau by migrating westwards. Along the colonization route, consecutive bottlenecks and surfing of rare alleles caused a significant reduction in genetic diversity and strong population differentiation. The direction and intensity of introgression from parental species varied among geographic regions. In western parts of its range, the species seems to have been isolated from seed and pollen flow from its parent species for a long time. The observed spatial distribution of genetic diversity in P. densata also appears to reflect the persistence of this species on the plateau during the last glaciation. Our results indicate that both ancient and contemporary population dynamics have contributed to the spatial distribution of genetic diversity in P. densata , which accordingly reflects its evolutionary history.

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

MpAsr encodes an intrinsically unstructured protein and enhances osmotic tolerance in transgenic Arabidopsis - Jin-Ran Dai; Bing Liu; Dong-Ru Feng; Hai-yan Liu; Yan-ming He; Kang-biao Qi; Hong-Bin Wang; Jin-Fa Wang (Plant Cell Reports, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

MeJA-inducible expression of the heterologous JAZ2 promoter from Arabidopsis in Populus trichocarpa protoplasts - Yin Wang; Guan-Jun Liu; Xiu-Feng Yan; Zhi-Gang Wei; Zhi-Ru Xu (Journal of Plant Diseases and Protection, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Asterotremella meifongana sp. nov. and Asterotremella nantouana sp. nov., two anamorphic basidiomycetous yeasts isolated from soil and mushrooms - Yi-Ru Liu; Li-Ying Huang; Suh-Shen Young; Chin-Feng Chang; Ching-Fu Lee (Antonie van Leeuwenhoek, 2011)

TGFBR1*6A/9A polymorphism and cancer risk: a meta-analysis of 13,662 cases and 14,147 controls - Ru-Yan Liao; Chen Mao; Li-Xin Qiu; Hong Ding; Qing Chen; Hai-Feng Pan (Molecular Biology Reports, 2010)

Genetic Analysis and Molecular Mapping of a Novel Gene Conferring Resistance to Rice Stripe Virus - Feng Zhao; Zhijun Cai; Tiezhu Hu; Haigen Yao; Li Wang; Na Dong; Bin Wang; Zhengang Ru; Wenxue Zhai (Plant Molecular Biology Reporter, 2010)

Segmentation of multispectral high-resolution satellite imagery using log Gabor filters - Pengfeng Xiao; Xuezhi Feng; Ru An; Shuhe Zhao (International Journal of Remote Sensing, 2010)

Cytological and RAPD data revealed genetic relationships among nine selected populations of the wild bramble species, Rubus parvifolius and R. coreanus (Rosaceae) - Xiao-rong Wang; Yuan Liu; Bi-feng Zhong; Xiao-li Dong; Qing Chen; Wu-feng Xia; Hanwu Zhang; Hao-ru Tang (Genetic Resources and Crop Evolution, 2010)

The production of sexual and asexual larvae within single broods of the scleractinian coral, Pocillopora damicornis - Shang-Ru Yeoh; Chang-Feng Dai (Marine Biology, 2010)

Solid-state fermentation of cornmeal with the ascomycete Morchella esculenta for degrading starch and upgrading nutritional value - Gui-Ping Zhang; Feng Zhang; Wen-Ming Ru; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2010)

Karyotypic, palynological, and RAPD study on 12 taxa from two subsections of section Idaeobatus in Rubus L. and taxonomic treatment of R. ellipticus, R. pinfaensis, and R. ellipticus var. obcordatus - Xiao-Rong Wang; Hao-Ru Tang; Han-Wu Zhang; Bi-Feng Zhong; Wu-Feng Xia; Yuan Liu (Plant Systematics and Evolution, 2009)

A new iridoid glycoside from Scrophularia ningpoensis - Zheng-Rui Niu; Ru-Feng Wang; Ming-Ying Shang; Shao-Qing Cai (Natural Product Research, 2009)

Genetic Diversity and Population Structure of Celosia argentea and Related Species Revealed by SRAP - Na Feng; Qie Xue; Qinghua Guo; Ru Zhao; Meili Guo (Biochemical Genetics, 2009)

Empirical assessment of the reproductive fitness components of the hybrid pine Pinus densata on the Tibetan Plateau - Jian-Feng Mao; Yue Li; Xiao-Ru Wang (Evolutionary Ecology, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

The Influence of Center of Rotation on the Assessment of Trabecular Bone Densitometric and Structural Properties - Zhi-Feng Sheng; Ru-Chun Dai; Xian-Ping Wu; Yu-Lin Ma; Kang Xu; Yu-Hai Zhang; Ye-Bin Jiang; Er-Yuan Liao (Annals of Biomedical Engineering, 2008)

Improved biodesulfurization of hydrodesulfurized diesel oil using Rhodococcus erythropolis and Gordonia sp. - Guo-Qiang Li; Shan-Shan Li; Shi-Wei Qu; Qing-Kun Liu; Ting Ma; Lin Zhu; Feng-Lai Liang; Ru-Lin Liu (Biotechnology Letters, 2008)

Viral protein synthesis is required for Enterovirus 71 to induce apoptosis in human glioblastoma cells - Shin-Ru Shih; Kuo-Feng Weng; Victor Stollar; Mei-Ling Li (Journal of NeuroVirology, 2008)

Long-term aerobic exercise protects the heart against ischemia/reperfusion injury via PI3 kinase-dependent and Akt-mediated mechanism - Kun-Ru Zhang; Hai-Tao Liu; Hai-Feng Zhang; Quan-Jiang Zhang; Qiu-Xia Li; Qiu-Jun Yu; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2007)

Isolation and characterization of a novel thermophilic Bacillus strain degrading long-chain n-alkanes - Lei Wang; Yun Tang; Shuo Wang; Ru-Lin Liu; Mu-Zhi Liu; Yan Zhang; Feng-Lai Liang; Lu Feng (Extremophiles, 2006)

Hypoxic postconditioning enhances the survival and inhibits apoptosis of cardiomyocytes following reoxygenation: role of peroxynitrite formation - Hai-Chang Wang; Hai-Feng Zhang; Wen-Yi Guo; Hui Su; Kun-Ru Zhang; Qiu-Xia Li; Wenli Yan; Xin L. Ma; Bernard L. Lopez; Theodore A. Christopher; Feng Gao (Apoptosis, 2006)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Estimation of atmospheric input of mercury to South Lake and Jingyue Pool - Feng-man Fang; Qi-chao Wang; Zhuang-wei Ma; Ru-hai Liu; Yu-hong Cao (Chinese Geographical Science, 2002)

Differential expression of RAB5A in human lung adenocarcinoma cells with different metastasis potential - Li Yu; Feng Hui-chen; Yu Chen; Rong Zou; Song Yan; Liu Chun-xiang; Wang Wu-ru; Pu Li (Clinical & Experimental Metastasis, 1999)

The effect of lanthanide chloride on abscisic acid and electron-transport activity of some crops - Fu Li Zeng; Ming Feng Zhang; Shao Min Zhou; Ji Gui Wu; Ru Wen Deng (Biological Trace Element Research, 1999)

Expression of glutamate receptor subunits 2/3 and 4 in the hypoglossal nucleus of the rat after neurectomy - Feng-Ru Tang; M.-K. Sim (Experimental Brain Research, 1997)